Tall tree and aboveground biomass dynamics in redwood forests during hydroclimate whiplash - Stephen C. Sillett; Mark E. Graham (Forest Ecology and Management, 2026)

Crustal growth and reworking of the Southern West African craton: Implications for regional tectonics - Nicolas Thébaud; Quentin Masurel; Luis A. Para-Avila; Aurélien Eglinger; Julien Perret; Augustin Yao Koffi; Ousmane Wane; Helen McFarlane; Graham Begg; Guillaume Duclaux; Mark W. Jessell; Olivier Vanderhaeghe; et al. (Earth-Science Reviews, 2026)

Gibbsite solubility and aluminum speciation in alkaline nuclear waste containing nitrate, nitrite, and phosphate - Trent R. Graham; Ashley R. Kennedy; Winnie Liu; Daria V. Boglaienko; Robert G. Felsted; Jacob G. Morton; Micah P. Prange; Mark E. Bowden; Teresa L. Lemmon; Marie S. Swita; Hsiu-Wen Wang; Michael D. Britton; et al. (Chemical Engineering Journal, 2026)

Catalyzing community-led conservation governance through integrated conservation and development in coastal Mozambique - Rafaella Lobo; Althea Skinner; Matthew Clark; Milton Xavier; Graham Epstein; Mark Andrachuk; Dalila Sequeira; Matheus De Nardo; Brendan Fisher; Shauna L. Mahajan (Marine Policy, 2026)

Engineering Development of a Bi-directional Arterial Cannula with Peripheral Access for Cardiopulmonary Bypass - Joel D. Graham; Thomas J. Roussel; Steven C. Koenig; Mark S. Slaughter (Cardiovascular Engineering and Technology, 2026)

Assessing and strengthening community‐based coastal governance - Mark Andrachuk; Graham Epstein; Shauna Mahajan; Zephania Arnold; Sinezio Junior; Dresy Lovasoa; Monalisa Mabandla; George W. Maina; Caroline Njeri; Samson Obiene; Geoffrey Odhiambo; Lenice Ojwang; et al. (Conservation Biology, 2026)
Community‐based coastal governance is essential for biodiversity conservation and sustainable livelihoods, yet many communities continue to face significant challenges in establishing and sustaining effective governance systems. We sought to improve understanding of the current status of community‐based coastal governance across five countries in the Southwest Indian Ocean (SWIO) region of Africa. Using the Elinor tool and data system, we examined how specific governance attributes relate to perceived social and ecological outcomes and sought insights for community‐managed areas (CMAs) in the SWIO region. Progress toward strong community‐based governance of CMAs has been uneven across the region and across governance attributes. Although some CMAs have established clearly defined management boundaries and property rights, many other CMAs are still working to improve some attributes, such as congruent regulations, transparency, accountability, and operational capacity. Perceived ecological and social outcomes correlated with different governance attributes. Perceived ecological outcomes were positively correlated with measures of property rights and local governance, whereas perceived social outcomes were correlated with local governance and operational capacity. The strength of CMA governance tended to improve in the first 5–10 years after establishment, then governance attributes plateaued or declined thereafter. These findings coincide with typical funding cycles, thus reinforcing the value of continued investment in community‐based coastal governance. Specifically, our findings point to the importance of providing long‐term capacity development and securing durable conservation finance to ensure the success of CMAs. More broadly, these findings contribute to a growing body of evidence of the importance of paying attention to when and how to leverage different types of support and capacity building.

Examining the structure of visual analogue scales to capture motivation to eat in fasting and post-meal conditions - Clarissa A. Dakin; Cristiana Duarte; Kristine Beaulieu; Nicola Buckland; Michelle Dalton; Anna Myers; Catherine Gibbons; Mark Hopkins; Graham Finlayson; Molly Blakemore; R. James Stubbs (Appetite, 2026)

Decolonising hydrology: Reflecting on positionalities for sustainable and just futures - Kwok P. Chun; Thanti Octavianti; Lori Bradford; Mark Reeves; Mohsen Nagheeby; Adeyemi Olusola; Ben C. Howard; Natalie Ceperley; Giulio Castelli; Albert Nkwasa; Yus Budiyono; Graham Strickert; et al. (Environmental Science & Policy, 2026)

Disturbance type shapes initial community assembly patterns of early seral forest ground beetles in southwest Oregon - Graham S. Frank; James R. LaBonte; Matthew G. Betts; Andrew J. Kroll; James W. Rivers; Jake Verschuyl; Mark E. Swanson; Meg A. Krawchuk (Forest Ecology and Management, 2026)

The Black Array of Broadband Absolute Radiometers Earth Radiation Imager: Science Requirements, Instrument Design, and Concept of Operations - Odele Coddington; Cameron Straatsma; Ginger Drake; Kush Tyagi; Michelle Stephens; Chris Yung; Nathan Tomlin; John Lehman; Chip Bollendonk; Paris Buedel; Katherine Catani; Beth Cervelli; et al. (Advances in Atmospheric Sciences, 2026)
The Black Array of Broadband Absolute Radiometers Earth Radiation Imager (BABAR-ERI) is a small, adaptable nadir-pointed pushbroom imager to measure Earth-leaving broadband radiance from 0.3 µm to 100 µm with higher information content than is currently measured by reducing radiometric uncertainty and enabling cloud-resolving spatial resolution. The three-instrument BABAR-ERI suite fits a 12U CubeSat form factor and contains co-registered science telescope channels for measuring shortwave (0.3 µm to 4.5 µm band) and total radiance (0.3 µm to 100 µm band), dual-channel on-board radiance stability monitors, and a visible-wavelength camera. Novel, 1 × 32 element, electrical-substitution radiometer pixels image the shortwave and total radiance in 1 km × 1 km co-registered ground footprints; longwave radiance (4.5 µm to 100 µm band) is derived from subtraction of the shortwave and total radiance. The dual-channel onboard stability monitors are radiance standard detectors, and their measurements, acquired concurrently with the science telescopes and at much different duty cycles for the dual channels, will be used to track and correct the degradation of the science channels. The single-channel, mid-visible camera facilitates geolocation pointing knowledge and provides scene context information and sub-pixel variability to facilitate measurement stability studies and enable process-level science studies at high spatial resolution. The detectors for the science channels and stability monitors are absolute, ambient-temperature, micro-fabricated, electrical-substitution radiometers with near-perfect optical absorptance across the measurement range from vertically aligned carbon nanotubes. The BABAR-ERI science channels will be characterized over the full measurement range and for variable Earth scenes and deep space temperatures during extensive ground calibrations.

Cumulative environmental exposures adversely impact social behaviour and are associated with dysregulation of genes and proteins involved in epigenetic, ribosomal, and immune regulation in male mice - Morgan C. Bucknor; Brooke A. Keating; Velda X. Han; Brian S. Gloss; Pinki Dey; Nader Aryamanesh; Lee L. Marshall; Mark E. Graham; Ruwani Dissanayake; Xianzhong Lau; Shrujna Patel; Stela P. Petkova; et al. (Inflammation Research, 2026)
Objective This study investigated how cumulative environmental exposures influence offspring behaviour and inflammation-related molecular signatures in the brain and peripheral immune system. Methods A novel "triple-hit" mouse model was developed using C57Bl/6JAusB mice (N = 70), combining preconceptual social stress, antenatal high-fat diet, and a postnatal immune challenge (poly(I:C), 10 mg/kg). At 12 weeks, offspring underwent behavioural tests relevant to neurodevelopmental disorders (NDDs), including the Elevated Plus Maze, 3-Chamber Social Preference, Self-Grooming, and Marble Burying. A composite NDD-risk index was calculated. Single-cell RNA sequencing (scRNA-seq) and bulk proteomics were performed on male triple-hit offspring to identify differentially expressed genes and proteins associated with inflammatory pathways. Results Male triple-hit offspring showed elevated NDD-related behavioural risk and social deficits, not observed in females. scRNA-seq revealed altered inflammatory and ribosomal pathways in brain glia and peripheral immune cells. Proteomic analysis showed decreased abundance of proteins involved in inflammation, translation, chromatin remodelling, and synaptic function in both brain and blood. Conclusion Combined environmental stressors may drive male-specific behavioural and inflammatory changes relevant to NDDs. The identification of overlapping inflammatory signatures in brain and peripheral immune cells supports a role for shared immune mechanisms in brain–immune axis dysfunction. However, these pathway-level findings should be interpreted as preliminary hypotheses and warrant independent validation to confirm their mechanistic significance.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Comparison of Early Seral Forest Bee Communities Following Clearcutting or Wildfire Depends on Stand Age and Nesting Guild - Graham S. Frank; James W. Rivers; Jake Verschuyl; Lincoln R. Best; Matthew G. Betts; Andrew J. Kroll; Mark E. Swanson; Meg A. Krawchuk (Journal of Forestry, 2026)

High-precision U–Pb dating and Hf isotopes of MARID zircons reveals multi-source, prolonged metasomatism of the Kaapvaal sub-continental lithospheric mantle - Molly K. Paul; Darin M. Schwartz; S. Andrew DuFrane; D. Graham Pearson; Mark D. Schmitz (Mineralogy and Petrology, 2025)
Mica-amphibole-rutile-ilmenite-diopside (MARID) xenoliths are unique examples of phlogopite-dominated mantle metasomatism hypothesized to correlate geochemically and petrologically to kimberlite and carbonate-rich olivine lamproite (formerly group II kimberlite) magmatism. Here, we investigate the linkage between MARID metasomatism and alkaline magmatism using multiple analytical techniques: in situ trace element major phase and zircon geochemistry, in situ Hf isotope and U–Pb zircon geochemistry and geochronology, and high-precision isotope dilution U–Pb zircon geochronology. We find that most zircons in the studied MARID suite from Kimberley (South Africa) crystallized over a protracted interval in the Late Cretaceous coeval with regional kimberlite volcanism, with one sample yielding Neoproterozoic and Mesoproterozoic dates that are broadly coeval with Proterozoic tectono-magmatic events. Notably, we observe that older metasomatic compositions and ages in zircon are not obscured by mantle storage or later metasomatic events. Our findings confirm that some MARID-like metasomatism occurred as early as the Proterozoic, evolving to form a viable lithospheric mantle source for carbonate-rich olivine lamproites. Zircon geochemistry and geochronology also document that MARID precursors are infiltrated and modified by later Cretaceous kimberlitic melts, resulting in their diverse geochemical and isotopic compositions.

Aotearoa New Zealand’s marine carbon cycle in a changing climate – Current understanding and future directions - Scott D. Nodder; Cliff S. Law; Erik Behrens; Sarah J. Bury; Antonia Cristi; Charine Collins; Kim I. Currie; Moira Décima; Alain De Verneil; Pablo C. Escobar‐Flores; Denise Fernandez; Mark P. Gall; et al. (New Zealand Journal of Marine and Freshwater Research, 2025)
The marine system plays a critical role in the global climate cycle, as a major control of atmospheric carbon dioxide (CO 2 ). Marine primary production (photosynthesis) and remineralisation of organic carbon (respiration, degradation) determine the amount of CO 2 sequestered in marine sediments and deep‐water environments on century to millennial timescales. The stocks and fluxes of the marine carbon cycle are susceptible to global climate change impacts and other anthropogenic activities that modify key processes. Oceanographic studies of the marine carbon cycle in Aotearoa New Zealand’s Exclusive Economic Zone (NZ EEZ) and Territorial Seas over past decades have provided broad knowledge across a complex and dynamic seascape, but there remain fundamental knowledge gaps that limit identification of and response to present and future anthropogenic threats. In particular, several areas of the EEZ have been under‐sampled and there are currently insufficient data to establish baselines and variability for the marine carbon cycle. We recommend that new observational technologies and ocean modelling applications be fully developed and utilised to enable development of robust predictive capability of our ocean’s response to human‐induced perturbations. Future focus on oceanic nature‐based solutions to accelerate CO 2 uptake will require improved knowledge of the marine carbon cycle in NZ’s EEZ.

Emerging and persistent organic pollutants in sediment cores from the Singapore Straits: Rising pharmaceuticals, variable caffeine and static PAHs - Christopher H. Vane; Raquel A. Lopes dos Santos; Olivia A. Graham; Benjamin P. Horton; Mark C. Kalra; Vicky Moss-Hayes (Marine Pollution Bulletin, 2025)

Calcite priming of a hydrothermal eruption at South Orakonui, Ngā Tamariki Geothermal Field, New Zealand - Mark P. Simpson; Michael D. Rosenberg; Cristian Montanaro; Duncan J. Graham (Journal of Volcanology and Geothermal Research, 2025)

Improved allometry and heartwood development of Sequoia sempervirens in secondary forests - Stephen C. Sillett; Alana R. Chin; Allyson L. Carroll; Mark E. Graham; Marie E. Antoine (Forest Ecology and Management, 2025)

Food-level predictors of self-reported liking and hedonic overeating: Putting ultra-processed foods in context - Graham Finlayson; Rebecca Allen; Angelika Baaij; Kristine Beaulieu; Nicola J. Buckland; Clarissa Dakin; Michelle Dalton; Ruairi O'Driscoll; Cristiana Duarte; Catherine Gibbons; Mark Hopkins; Graham Horgan; et al. (Appetite, 2025)

Quantification of In Situ Ulnar Nerve Strain and Constraint Tension in the Forearm - Mark Carl Miller; Patrick J. Schimoler; Harsh Shah; Alexander Kharlamov; R. David Graham; Carol Armstrong; Andrew Wroblewski; Yue Yin; Peter Tang (Annals of Biomedical Engineering, 2025)

A phytol εp-based core-top calibration to reconstruct past changes in atmospheric CO2 - Olivia A. Graham; Caitlyn R. Witkowski; Mark A. Stevenson; Francien Peterse; B. David A. Naafs (Geochimica et Cosmochimica Acta, 2025)

Cross-scale patterns of structure and maximum biomass in late-seral Douglas-fir-dominated rainforests - Russell D. Kramer; Stephen C. Sillett; Sean M.A. Jeronimo; Mark E. Graham; Miles E. LeFevre; Allyson L. Carroll; Robert Van Pelt (Forest Ecology and Management, 2025)

Can badger vaccination contribute to bovine TB control? A narrative review of the evidence - Andrew Robertson; Mark A. Chambers; Graham C. Smith; Richard J. Delahay; Robbie A. McDonald; Peter N.M. Brotherton (Preventive Veterinary Medicine, 2025)

Machine-learning based spatiotemporal performance analysis of degraded tropical peatland groundwater level numerical model - Iman Salehi Hikouei; Keith N. Eshleman; Bambang Hero Saharjo; Laura L.B. Graham; Grahame Applegate; Mark A. Cochrane (Groundwater for Sustainable Development, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Marginal abatement cost curves of climate-smart agricultural practices to mitigate greenhouse gas emissions from smallholder dairy farms in Kenya - Mark E. Caulfield; Michael Graham; James Gibbons; Louise McNicol; Prysor Williams; Dave Chadwick; Jesse Gakige; Andreas Wilkes; Bernard Kimoro; Claudia Arndt (Journal of Cleaner Production, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Balancing boat‐electrofishing sampling effort against costs for nearshore fish communities in the Toronto waterfront, Lake Ontario - Sebastian Theis; Angela Wallace; Brian Graham; Brynn Coey; Lyndsay Cartwright; Mark Poesch; Rick Portiss; Jonathan L. W. Ruppert (Fisheries Management and Ecology, 2025)
To enhance management of aquatic systems, long‐term monitoring programs are crucial. However, managers often lack sufficient guidance in decision‐making. In this study, we analyzed nearshore electrofishing data from Lake Ontario spanning 18 years and over 100,000 caught fish to assess sampling designs for various coastal habitats. Using simulation, we evaluated precision of catch per unit effort (CPUE) for all species, piscivores, and specialist species, at different levels of electrofishing sampling effort. For overall CPUE in any habitat type, increased precision declined with additional electrofishing runs, particularly after reaching 30–40 runs. Adjustments in sampling effort, such as adding 10 runs per year for open‐coast sites, increased precision of overall CPUE by 10%. Adding 8 runs per year for wetlands increased precision of specialist‐species CPUE by 10%. However, additional runs in embayments did not increase precision for all species, piscivores, or specialist species. Our findings underscore the importance of considering community composition and abundance when evaluating CPUE precision and illustrates a flexible approach to optimize sampling effort in aquatic monitoring programs.

Antimicrobial resistant Enterobacterales of clinical importance in mute swans - Aneta Kovarova; Graham Prole; Maeve Louise Farrell; Mark Maguire; Louise Catherine Murphy; Alexandra Chueiri; Louise O'Connor; Georgios Miliotis; Dearbháile Morris; Liam P. Burke (Science of The Total Environment, 2025)

Analyzing Archive Transit Multibeam Data for Nodule Occurrences - Mark E. Mussett; David F. Naar; David W. Caress; Tracey A. Conrad; Alastair G. C. Graham; Max Kaufmann; Marcia Maia (Journal of Marine Science and Engineering, 2024)
We show that analyzing archived and future multibeam backscatter and bathymetry data, in tandem with regional environmental parameters, can help to identify polymetallic nodule fields in the world’s oceans. Extensive archived multibeam transit data through remote areas of the world’s oceans are available for data mining. New multibeam data will be made available through the Seabed 2030 Project. Uniformity of along- and across-track backscatter, backscatter intensity, angular response, water depth, nearby ground-truth data, local slope, sedimentation rate, and seafloor age provide thresholds for discriminating areas that are permissive to nodule presence. A case study of this methodology is presented, using archived multibeam data from a remote section of the South Pacific along the Foundation Seamounts between the Selkirk paleomicroplate and East Pacific Rise, that were collected during the 1997 Foundation–Hotline expedition on R/V Atalante. The 12 kHz Simrad EM12D multibeam data and the other forementioned data strongly suggest that a previously unknown nodule occurrence exists along the expedition transit. We also compare the utility of three different backscatter products to demonstrate that scans of printed backscatter maps can be a useful substitute for digital backscatter mosaics calculated using primary multibeam data files. We show that this expeditious analysis of legacy multibeam data could characterize benthic habitat types efficiently in remote deep-ocean areas, prior to more time-consuming and expensive video and sample acquisition surveys. Additionally, utilizing software other than specialty sonar processing programs during this research allows an exploration of how multibeam data products could be interrogated by a broader range of scientists and data users. Future mapping, video, and sampling cruises in this area would test our prediction and investigate how far it might extend to the north and south.

Threat assessment for Pacific sand lance (Ammodytes personatus) in the Salish Sea - Jacqueline R. Huard; Victoria Hemming; Matthew R. Baker; Jennifer Blancard; Ian Bruce; Sarah Cook; Gail K. Davoren; Phillip Dionne; Virginia East; J. Mark Hipfner; Nicola R. Houtman; Brian A. Koval; et al. (Frontiers in Marine Science, 2024)
Like many forage fish species, Pacific sand lance ( Ammodytes personatus ) play a key role in nearshore marine ecosystems as an important prey source for a diverse array of predators in the northeastern Pacific. However, the primary threats to Pacific sand lance and their habitat are poorly defined due to a lack of systematic data. Crucial information needed to assess their population status is also lacking including basic knowledge of their local and regional abundance and distribution. Sand lance are currently listed as ‘not evaluated’ under the IUCN red list and they have not been assessed by US and Canadian agencies. This hampers management and policy efforts focused on their conservation. To address this knowledge gap, we conducted a three-part, structured expert elicitation to assess the vulnerability of Salish Sea sand lance populations. Experts were asked to list and rank key threats to Salish Sea sand lance and/or their habitat, to further quantify the vulnerability of sand lance to identified threats using a vulnerability matrix, and to predict the population trajectory in 25 years from today. Impacts associated with climate change (e.g. sea level rise, sea temperature rise, ocean acidification, and extreme weather) consistently ranked high as threats of concern in the ranking exercise and quantified vulnerability scores. Nearly every expert predicted the population will have declined from current levels in 25 years. These results suggest sand lance face numerous threats and may be in decline under current conditions. This research provides vital information about which threats pose the greatest risk to the long-term health of sand lance populations and their habitat. Managers can use this information to prioritize which threats to address. Future research to reliably quantify population size, better understand the roles of natural and anthropogenic impacts, and to identify the most cost-effective actions to mitigate multiple threats, is recommended.

Potential drivers of changing ecological conditions in English and Welsh rivers since 1990 - Emma Pharaoh; Mark Diamond; Helen P. Jarvie; Steve J. Ormerod; Graham Rutt; Ian P. Vaughan (Science of The Total Environment, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Ground-based calibration for remote sensing of biomass in the tallest forests - Stephen C. Sillett; Mark E. Graham; John P. Montague; Marie E. Antoine; George W. Koch (Forest Ecology and Management, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Drought impact on pharmaceuticals in surface waters in Europe: Case study for the Rhine and Elbe basins - Mark P. Lentz; Duncan J. Graham; Michelle T.H. van Vliet (Science of The Total Environment, 2024)

Cloudwork als Chance für den Globalen Süden? - Tatiana López; Patrick Feuerstein; Janine de Vera; Giulia Varaschin; Zeynep Karlıdağ; Mark Graham (Standort, 2024)
Zusammenfassung Online-Plattformarbeit – auch als „Cloudwork“ bekannt – hat in den letzten Jahren ein rasantes Wachstum verzeichnet. Entwicklungspolitische Debatten betonen in diesem Zusammenhang die neuen Einkommens- und professionellen Entwicklungschancen für gut ausgebildete, jedoch oft unterbeschäftigte Arbeiter*innen aus Ländern des Globalen Südens. Cloudwork-Plattformen bieten diesen Arbeiter*innen neue Zugänge zu Kund*innen und Aufträgen aus dem Globalen Norden, die in Dollar oder Euro vergütet werden. Gleichzeitig zeigen Studien jedoch, dass Online-Plattformarbeit oftmals mit unsicheren Bedingungen und psychischen Belastungen einhergeht. Dieser Beitrag untersucht die Einkommens- und professionellen Entwicklungschancen von Online-Plattformarbeiter*innen aus dem Globalen Süden im Übersetzungs- und Transkriptionssektor. Er stützt sich auf eine quantitative Online-Befragung mit 401 Plattformarbeiter*innen (darunter 266 aus dem Globalen Süden), die im Jahr 2022 im Rahmen des Fairwork-Projekts durchgeführt wurde. Die Ergebnisse zeigen, dass die Einkommens- und professionellen Entwicklungschancen von Cloud-Arbeiter*innen durch ihre geographische Verortung und die Art der Arbeitsorganisation auf den einzelnen Plattformen beeinflusst werden. Arbeiter*innen aus dem Globalen Süden mussten im Vergleich zu ihren Kolleg*innen aus dem Globalen Norden mehr unbezahlte Arbeitszeit (z. B. in die Suche nach Jobs) investieren. Trotzdem konnten Arbeiter*innen aus dem Globalen Süden auch unter Einberechnung der unbezahlten Arbeitsstunden eher ein Einkommen über dem lokalen Mindestlohnniveau erzielen – eine Tatsache, die sich durch internationale Unterschiede in den lokalen Lohnniveaus erklären lässt. Unbezahlte Arbeitszeit ist besonders ausgeprägt auf sogenannten „Micro-Task-Plattformen“ im Transkriptionssektor, da hier das Überangebot von Arbeitskräften in der Regel sehr hoch ist. Insgesamt verdeutlicht unser Beitrag die Machtposition von Plattformunternehmen, welche neue globale Geographien der Online-Arbeit hervorbringen und kontrollieren, und damit Chancen für gute Arbeit im Globalen Süden beeinflussen.

No effect of prefrontal transcranial direct current stimulation (tDCS) on food craving, food reward and subjective appetite in females displaying mild-to-moderate binge-type behaviour - Jordan D. Beaumont; Michelle Dalton; Danielle Davis; Graham Finlayson; Alexander Nowicky; Mark Russell; Martin J. Barwood (Appetite, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Environmental and genetic variation in an asexual plant - Mark Davidson Jewell; Graham Bell (Aquatic Botany, 2023)

Eco‐evolutionary contributions to community trait change in floating aquatic plants - Mark Davidson Jewell; Graham Bell (Ecology, 2023)
An entire community of organisms may become modified when its environment changes. These modifications can happen through physiological processes (plasticity), evolutionary processes (adaptation) or shifts in species composition (sorting). The outcome of these three sources of change constitutes the community's phenotypic response, but how they combine to drive community trait dynamics is not currently well understood. We have conducted a community selection experiment in which communities of short‐lived floating aquatic plants were grown in a range of stressful conditions, and measured changes in their body size. Determinants of phenotypic change were assessed with a full community reciprocal transplant which led to estimates of the contributions of plasticity, adaptation, and sorting. Species were modified during the experiment by both plasticity and adaptation, but in either case the magnitude and direction of change differed among species. Sorting and adaptation were of equal magnitude but tended to act in opposite directions: in conditions where species with large fronds prevailed, each species evolved smaller fronds, and vice versa. We conclude that community trait dynamics cannot be understood simply by extrapolating the adaptive response of any single species to the whole community.

Geographical distribution of floating aquatic plants in relation to environmental conditions in southern Quebec, Canada - Mark Davidson Jewell; Sofia J. van Moorsel; Graham Bell (Aquatic Botany, 2023)

Recent progress on understanding coronal mass ejection/flare onset by a NASA living with a star focused science team - Mark G. Linton; Spiro K. Antiochos; Graham Barnes; Yuhong Fan; Yang Liu; Benjamin J. Lynch; Andrey N. Afanasyev; C. Nick Arge; Joan Burkepile; Mark C.M. Cheung; Joel T. Dahlin; Marc L. DeRosa; et al. (Advances in Space Research, 2023)

Evidence of biological recovery from gross pollution in English and Welsh rivers over three decades - Emma Pharaoh; Mark Diamond; Steve J. Ormerod; Graham Rutt; Ian P. Vaughan (Science of The Total Environment, 2023)

Temporal evolution of shallow marine diagenetic environments: Insights from carbonate concretions - Sean J. Loyd; Patrick Meister; Bo Liu; Kevin Nichols; Frank A. Corsetti; Robert Raiswell; William Berelson; Graham Shields; Mark Hounslow; John W.F. Waldron; Bayne Westrick-Snapp; Jamie Hoffman (Geochimica et Cosmochimica Acta, 2023)

Overwintering and re-emergence in Lemna minor - Mark Davidson Jewell; Graham Bell (Aquatic Botany, 2023)

Zinc on the edge—isotopic and geophysical evidence that cratonic edges control world-class shale-hosted zinc-lead deposits - David L. Huston; David C. Champion; Karol Czarnota; Jingming Duan; Matthew Hutchens; Suzanne Paradis; Mark Hoggard; Bryant Ware; George M. Gibson; Michael P. Doublier; Karen Kelley; Anne McCafferty; et al. (Mineralium Deposita, 2023)
The North Australian Zinc Belt is the largest zinc-lead province in the world, containing three of the ten largest known individual deposits (HYC, Hilton-George Fisher, and Mount Isa). The Northern Cordillera in North America is the second largest zinc-lead province, containing a further two of the world’s top ten deposits (Red Dog and Howards Pass). Despite this world-class endowment, exploration in both mineral provinces during the past 2 decades has not been particularly successful, yielding only two significant discoveries (Teena, Australia, and Boundary, Canada). One of the most important aspects of exploration is to choose mineral provinces and districts within geological belts that have the greatest potential for discovery. Here, we present results from these two zinc belts that highlight previously unused datasets for area selection and targeting. Lead isotope mapping using analyses of mineralized material has identified gradients in μ ( 238 U/ 204 Pb) that coincide closely with many major deposits. Locations of these deposits also coincide with a gradient in the depth of the lithosphere-asthenosphere boundary determined from calibrated surface wave tomography models converted to temperature. Furthermore, gradients in upward-continued gravity anomalies and a step in Moho depth correspond to a pre-existing major crustal boundary in both zinc belts. A spatial association of deposits with a linear mid- to lower-crustal resistivity anomaly from magnetotelluric data is also observed in the North Australian Zinc Belt. The change from thicker to thinner lithosphere is interpreted to localize prospective basins for zinc-lead mineralization and to control the gradient in lead isotope and geophysical data. These data, when combined with data indicative of paleoenvironment and changes in plate motion at the time of mineralization, provide new exploration criteria that can be used to identify prospective mineralized basins and define the most favorable parts of these basins.

Great expectations: patients’ preferences for clinically significant results from genomic sequencing - Salma Shickh; Agnes Sebastian; Marc Clausen; Chloe Mighton; Christine Elser; Andrea Eisen; Larissa Waldman; Seema Panchal; Thomas Ward; June C. Carroll; Emily Glogowski; Kasmintan A. Schrader; et al. (Human Genetics, 2023)

Linking human impacts to community processes in terrestrial and freshwater ecosystems - Ian R. McFadden; Agnieszka Sendek; Morgane Brosse; Peter M. Bach; Marco Baity‐Jesi; Janine Bolliger; Kurt Bollmann; Eckehard G. Brockerhoff; Giulia Donati; Friederike Gebert; Shyamolina Ghosh; Hsi‐Cheng Ho; et al. (Ecology Letters, 2023)
Human impacts such as habitat loss, climate change and biological invasions are radically altering biodiversity, with greater effects projected into the future. Evidence suggests human impacts may differ substantially between terrestrial and freshwater ecosystems, but the reasons for these differences are poorly understood. We propose an integrative approach to explain these differences by linking impacts to four fundamental processes that structure communities: dispersal, speciation, species‐level selection and ecological drift. Our goal is to provide process‐based insights into why human impacts, and responses to impacts, may differ across ecosystem types using a mechanistic, eco‐evolutionary comparative framework. To enable these insights, we review and synthesise (i) how the four processes influence diversity and dynamics in terrestrial versus freshwater communities, specifically whether the relative importance of each process differs among ecosystems, and (ii) the pathways by which human impacts can produce divergent responses across ecosystems, due to differences in the strength of processes among ecosystems we identify. Finally, we highlight research gaps and next steps, and discuss how this approach can provide new insights for conservation. By focusing on the processes that shape diversity in communities, we aim to mechanistically link human impacts to ongoing and future changes in ecosystems.

Using machine learning algorithms to predict groundwater levels in Indonesian tropical peatlands - Iman Salehi Hikouei; Keith N. Eshleman; Bambang Hero Saharjo; Laura L.B. Graham; Grahame Applegate; Mark A. Cochrane (Science of The Total Environment, 2023)

Controlling the oligomeric composition and char yield of pyrene pitches via continuous supercritical extraction - W. Cabell Lamie; Graham W. Tindall; Wesley P. Hoffman; Mark C. Thies (Fuel, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Climate impacts alter fisheries productivity and turnover on coral reefs - Mark Hamilton; James P. W. Robinson; Cassandra E. Benkwitt; Shaun K. Wilson; M. Aaron MacNeil; Ameer Ebrahim; Nicholas A. J. Graham (Coral Reefs, 2022)
Alteration of benthic reef habitat after coral bleaching and mortality induces changes in fish assemblages, with implications for fisheries. Our understanding of climate impacts to coral reef fisheries is largely based on fish abundance and biomass. The rates at which biomass is produced and replenished (productivity and turnover) are also important to sustaining fisheries, yet the responses of these metrics following bleaching are largely unknown. Here, we examine changes in fish productivity and turnover after mass coral bleaching events in Seychelles, on reefs that were recovering to coral-dominated habitats and those that shifted to macroalgae-dominated regimes. Productivity of fish assemblages increased on all recovering reefs, particularly on fished reefs resulting in levels similar to protected reefs 19 years after bleaching. Herbivore-detritivores, such as scraping and excavating parrotfish, appeared to drive biomass production through increased abundance on recovering reefs. Productivity on regime-shifted reefs remained stable at 1994 levels in fished areas, with increases observed on protected reefs. Large increases in browser productivity (particularly on protected reefs), combined with increases for invertivores, maintained post-bleaching productivity on macroalgal reefs. For all diet groups, net turnover was generally higher on fished regime-shifted reefs than on recovering reefs, suggesting fish biomass is more readily replenished on macroalgal reefs. Reef structural complexity was a positive predictor of productivity for all diet groups. These findings indicate that post-bleaching reef fish productivity is strongly influenced by benthic recovery trajectories, and demonstrates the importance of herbivore and invertivore species in sustaining small-scale inshore fisheries following climatic disturbances.

Enhancement in soil fertility, early plant growth and nutrition and mycorrhizal colonization by vermicompost application varies with native and exotic tree species - Jianming Xue; Mark R. Bakker; Sylvie Milin; Doug Graham (Journal of Soils and Sediments, 2022)
Purpose The impact of vermicompost on tree-soil systems is not yet fully understood. This study aimed to comparatively investigate the effects of chemical fertilizer, compost and vermicompost on soil enzymatic activities, seedling mycorrhizal colonization, growth and nutrition of one exotic tree species (radiata pine, Pinus radiata D. Don) and two native tree species (mānuka, Leptospermum scoparium and tōtara, Podocarpus totara ). Methods A 12-month-long pot trial was set up in the glasshouse with a factorial design of three tree species (radiata pine, tōtara and manuka) by six treatments, including T1-control, T2-chemical fertilizer, T3-HS compost, T4-HS vermicompost, T5-LS vermicompost and T6-CM vermicompost. We assessed the main effects and interactions of treatment and species on soil chemical and biological properties, plant growth and nutritional responses. Results Compared to the untreated control (T1), application of vermicomposts (T4-T6) and compost (T3) significantly improved soil chemical properties and enzymatic activities, and increased total seedling dry weight by 160–260%, shoot concentrations of nitrogen (N) by 54–97% and phosphorus (P) by 61–91%. Vermicomposts were comparable to diammonium phosphate (DAP) applied at 133 kg N ha −1 (T2) in stimulating the growth of native species (mānuka and tōtara) without negative impact on mycorrhizal colonization, with T5 being better than DAP (T2) in promoting mānuka growth. However, application of vermicompost alone was less effective than DAP in stimulating the exotic radiata pine growth. Overall, soil activities of dehydrogenase, urease, acid phosphatase and invertase were significantly and positively correlated to total C and N and exchangeable Ca and Mg. Conclusion The increased growth of three tree species after application of vermicomposts was mainly related to improved N and P nutrition associated with enhanced root growth and soil enzymatic activities. Our findings imply that the vermicomposting products from septic tank waste could be a promising alternative to inorganic fertilizers in land application or greenhouse potting media of native tree species.

Trait groups as management entities in a complex, multispecies reef fishery - Louise Anderson; Peter Houk; Mark G. R. Miller; Javier Cuetos‐Bueno; Curtis Graham; Kriskitina Kanemoto; Elizabeth Terk; Elizabeth McLeod; Maria Beger (Conservation Biology, 2022)
Localized stressors compound the ongoing climate‐driven decline of coral reefs, requiring natural resource managers to work with rapidly shifting paradigms. Trait‐based adaptive management (TBAM) is a new framework to help address changing conditions by choosing and implementing management actions specific to species groups that share key traits, vulnerabilities, and management responses. In TBAM maintenance of functioning ecosystems is balanced with provisioning for human subsistence and livelihoods. We first identified trait‐based groups of food fish in a Pacific coral reef with hierarchical clustering. Positing that trait‐based groups performing comparable functions respond similarly to both stressors and management actions, we ascertained biophysical and socioeconomic drivers of trait‐group biomass and evaluated their vulnerabilities with generalized additive models. Clustering identified 7 trait groups from 131 species. Groups responded to different drivers and displayed divergent vulnerabilities; human activities emerged as important predictors of community structuring. Biomass of small, solitary reef‐associated species increased with distance from key fishing ports, and large, solitary piscivores exhibited a decline in biomass with distance from a port. Group biomass also varied in response to different habitat types, the presence or absence of reported dynamite fishing activity, and exposure to wave energy. The differential vulnerabilities of trait groups revealed how the community structure of food fishes is driven by different aspects of resource use and habitat. This inherent variability in the responses of trait‐based groups presents opportunities to apply selective TBAM strategies for complex, multispecies fisheries. This approach can be widely adjusted to suit local contexts and priorities.

Physical activity and glioma: a case–control study with follow-up for survival - Zohreh Basiri; Yi Yang; Fiona J. Bruinsma; Anna K. Nowak; Kerrie L. McDonald; Katharine J. Drummond; Mark A. Rosenthal; Eng-Siew Koh; Rosemary Harrup; Elizabeth Hovey; David Joseph; Geza Benke; et al. (Cancer Causes & Control, 2022)
Purpose High-grade disease accounts for ~ 70% of all glioma, and has a high mortality rate. Few modifiable exposures are known to be related to glioma risk or mortality. Methods We examined associations between lifetime physical activity and physical activity at different ages (15–18 years, 19–29 years, 30–39 years, last 10 years) with the risk of glioma diagnosis, using data from a hospital-based family case–control study (495 cases; 371 controls). We followed up cases over a median of 25 months to examine whether physical activity was associated with all-cause mortality. Physical activity and potential confounders were assessed by self-administered questionnaire. We examined associations between physical activity (metabolic equivalent [MET]-h/wk) and glioma risk using unconditional logistic regression and with all-cause mortality in cases using Cox regression. Results We noted a reduced risk of glioma for the highest (≥ 47 MET-h/wk) versus lowest (< 24 METh/wk) category of physical activity for lifetime activity (OR = 0.58, 95% CI: 0.38–0.89) and at 15–18 years (OR = 0.57, 95% CI: 0.39–0.83). We did not observe any association between physical activity and all-cause mortality (HR for lifetime physical activity = 0.91, 95% CI: 0.64–1.29). Conclusion Our findings are consistent with previous research that suggested physical activity during adolescence might be protective against glioma. Engaging in physical activity during adolescence has many health benefits; this health behavior may also offer protection against glioma.

Paleoproterozoic gold events in the southern West African Craton: review and synopsis - Quentin Masurel; Aurélien Eglinger; Nicolas Thébaud; Andrew Allibone; Anne-Sylvie André-Mayer; Helen McFarlane; John Miller; Mark Jessell; Laurent Aillères; Olivier Vanderhaeghe; Stefano Salvi; Lenka Baratoux; et al. (Mineralium Deposita, 2022)

Effect of expansion of human umbilical cord blood CD34 + cells on neurotrophic and angiogenic factor expression and function - Ashalyn P. Watt; Mark Kirkland; Lakshmi Nekkanti; Yen Pham; Courtney McDonald; Atul Malhotra; Guy Moeneclaey; Suzanne L. Miller; Graham Jenkin (Cell and Tissue Research, 2022)
The use of CD34 + cell-based therapies has largely been focused on haematological conditions. However, there is increasing evidence that umbilical cord blood (UCB) CD34 + -derived cells have neuroregenerative properties. Due to low cell numbers of CD34 + cells present in UCB, expansion is required to produce sufficient cells for therapeutic purposes, especially in adults or when frequent applications are required. However, it is not known whether expansion of CD34 + cells has an impact on their function and neuroregenerative capacity. We addressed this knowledge gap in this study, via expansion of UCB-derived CD34 + cells using combinations of LDL, UM171 and SR-1 to yield large numbers of cells and then tested their functionality. CD34 + cells expanded for 14 days in media containing UM171 and SR-1 resulted in over 1000-fold expansion. The expanded cells showed an up-regulation of the neurotrophic factor genes BDNF, GDNF, NTF-3 and NTF-4, as well as the angiogenic factors VEGF and ANG. In vitro functionality testing showed that these expanded cells promoted angiogenesis and, in brain glial cells, promoted cell proliferation and reduced production of reactive oxygen species (ROS) during oxidative stress. Collectively, this study showed that our 14-day expansion protocol provided a robust expansion that could produce enough cells for therapeutic purposes. These expanded cells, when tested in in vitro, maintained functionality as demonstrated through promotion of cell proliferation, attenuation of ROS production caused by oxidative stress and promotion of angiogenesis.

Deep aspirations: towards a sustainable offshore Blue Economy - Camilla Novaglio; Narissa Bax; Fabio Boschetti; Gholam Reza Emad; Stewart Frusher; Liam Fullbrook; Mark Hemer; Sarah Jennings; Ingrid van Putten; Lucy M. Robinson; Erica Spain; Joanna Vince; et al. (Reviews in Fish Biology and Fisheries, 2022)

Fields with no recent legume cultivation have sufficient nitrogen-fixing rhizobia for crops of faba bean (Vicia faba L.) - Marta Maluk; Francesc Ferrando-Molina; Laura Lopez del Egido; Adrian Langarica-Fuentes; Genet Gebre Yohannes; Mark W. Young; Peter Martin; Richard Gantlett; Greg Kenicer; Cathy Hawes; Graham S. Begg; Richard S. Quilliam; et al. (Plant and Soil, 2022)
Purpose (1) To assess the biological N fixation (BNF) potential of varieties of faba bean ( Vicia faba L.) cropped with or without compost in an experimental field-scale rotation with no recent history of legumes, (2) to enumerate soil populations of Rhizobium leguminosarum sv. viciae ( Rlv ), and to genetically characterize the nodulating Rlv strains, (3) compare BNF with other sites in Britain. Methods BNF was evaluated from 2012 to 2015 using 15 N natural abundance. Treatments were either PK fertilizer or compost. Soil rhizobial populations were determined using qPCR, the symbiotic rhizobia genotyped (16 S rRNA, nodA and nodD genes), and their BNF capacity assessed ex situ . The reliance of legumes on BNF at other British sites was estimated in a single season, and their nodulating symbionts examined. Results Faba bean obtained most of its N through BNF (>80%) regardless of variety or year. N-accumulation by cvs Babylon and Boxer increased with compost treatment in 2014/2015. Rhizobial populations were c. 10 5 -10 6 Rlv cells g −1 soil regardless of field or treatment. 157 Rlv microsymbionts grouped into two large nodAD clades; one mainly from V. faba , and the other from various legumes. All isolates nodulated, and some performed better than commercial inoculant strains. Conclusions Faba bean can provide most of its nitrogen through BNF and leave economically valuable residual N for subsequent crops. Recent legume cropping in northern Europe is not essential for effective nodulation: rhizobia may persist in a range of farmland locations. Nevertheless, there is the potential to apply elite rhizobial strains as inoculants in some soils.

Area‐based management of blue water fisheries: Current knowledge and research needs - Ray Hilborn; Vera N. Agostini; Milani Chaloupka; Serge M. Garcia; Leah R. Gerber; Eric Gilman; Quentin Hanich; Amber Himes‐Cornell; Alistair J. Hobday; David Itano; Michel J. Kaiser; Hilario Murua; et al. (Fish and Fisheries, 2022)
The pelagic fisheries beyond the continental shelves are currently managed with a range of tools largely based on regulating effort or target catch. These tools comprise both static and dynamic area‐based approaches to include gear limitations, closed areas and bycatch limits. There are increasing calls for additional area‐based interventions, particularly expansion of marine protected areas, with many now advocating closing 30% of the oceans to fishing. In this paper, we review the objectives, methods and successes of area‐based management of blue water fisheries across objectives related to food production and environmental, social and economic impacts. We also consider the methods used to evaluate the performance of area‐based regulations and provide a summary of the relative quality of evidence from alternative evaluation approaches. We found that few area‐based approaches have been rigorously evaluated, and that it is often difficult to obtain requisite observational data to define a counterfactual to infer any causal effect for such evaluation. Management agencies have been relatively successful at maintaining important commercial species at or near their target abundance, but success at meeting ecological or social goals is less clear. The high mobility of both target and bycatch species generally reduces the effectiveness of area‐based management, and shifting distributions due to climate change suggest that adaptive rather than static approaches will be preferred. We prioritize research and management actions that would make area‐based management more effective.

Attributing Controlling Factors of Acidification and Hypoxia in a Deep, Nutrient-Enriched Estuarine Embayment - John R. Zeldis; Kim I. Currie; Scott L. Graham; Mark P. Gall (Frontiers in Marine Science, 2022)
Measuring and attributing controlling factors of acidification and hypoxia are essential for management of coastal ecosystems affected by those stressors. We address this using surveys in the Firth of Thames, a deep, seasonally stratified estuarine embayment adjoing the Hauraki Gulf in northern Aotearoa/New Zealand. The Firth’s catchment has undergone historic land-use intensification transforming it from native forest cover to dominance by pastoral use, increasing its riverine total nitrogen loading by ∼82% over natural levels and switching it’s predominate loading source from offshore to the catchment. We hypothesised that seasonal variation in net ecosystem metabolism [NEM: dissolved inorganic carbon (DIC) uptake/release] will be a primary factor determining carbonate and oxic responses in the Firth, and that organic matter involved in the metabolism will originate primarily by fixation within the Firth system and be driven by catchment dissolved inorganic nitrogen (DIN) loading. Seasonal ship-based and biophysical mooring surveys across the Hauraki Gulf and Firth showed depressed pH and O 2 reaching pH ∼7.8 and O 2 ∼4.8 mg L –1 in autumn in the inner Firth, matched by shoreward increasing nutrient loading, phytoplankton, organic matter, gross primary production (GPP) and apparent O 2 utilization. A carbonate system deconvolution of the ship survey data, combined with other ship survey and mooring results, showed how CO 2 partial pressure responded to seasonal shifts in temperature, NEM, phytoplankton sinking and mineralisation and water column stratification, that underlay the late-season expression of acidification and hypoxia. This aligned with seasonal shifts in net DIC fluxes determined in a coincident nutrient mass-balance analysis, showing near-neutral fluxes from spring to summer, but respiratory NEM from summer to autumn. Particulate C:N and ratios of organic C fixed by Firth GPP to that from river inputs (∼29- to 100-fold in summer and autumn) showed that the dominant source of organic matter fuelling heterotrophy in autumn was autochthonous GPP, driven by riverine DIN loading. The results signified the sensitivity of deep, long-residence time, seasonally stratifying estuaries to acidification and hypoxia, and are important for coastal resource management, including aquaculture developments and catchment runoff limit-setting for maintenance of ecosystem health.

Modelling the effects of cold temperature during the reproductive stage on the yield of chickpea (Cicer arietinum L.) - Muhuddin Rajin Anwar; David J. Luckett; Yashvir S. Chauhan; Ryan H. L. Ip; Lancelot Maphosa; Marja Simpson; Annie Warren; Rosy Raman; Mark F. Richards; Georgina Pengilley; Kristy Hobson; Neroli Graham (International Journal of Biometeorology, 2022)
During the reproductive stage, chilling temperatures and frost reduce the yield of chickpea and limit its adaptation. The adverse effects of chilling temperature and frost in terms of the threshold temperatures, impact of cold duration, and genotype-by-environment-by-management interactions are not well quantified. Crop growth models that predict flowering time and yield under diverse climates can identify combinations of cultivars and sowing time to reduce frost risk in target environments. The Agricultural Production Systems Simulator (APSIM-chickpea) model uses daily temperatures to model basic crop growth but does not include penalties for either frost damage or cold temperatures during flowering and podding stages. Regression analysis overcame this limitation of the model for chickpea crops grown at 95 locations in Australia using 70 years of historic data incorporating three cultivars and three sowing times (early, mid, and late). We modified model parameters to include the effect of soil water on thermal time calculations, which significantly improved the prediction of flowering time. Simulated data, and data from field experiments grown in Australia (2013 to 2019), showed robust predictions for flowering time ( n = 29; R 2 = 0.97), and grain yield ( n = 22; R 2 = 0.63–0.70). In addition, we identified threshold cold temperatures that significantly affected predicted yield, and combinations of locations, variety, and sowing time where the overlap between peak cold temperatures and peak flowering was minimal. Our results showed that frost and/or cold temperature–induced yield losses are a major limitation in some unexpected Australian locations, e.g., inland, subtropical latitudes in Queensland. Intermediate sowing maximise yield, as it avoids cold temperature, late heat, and drought stresses potentially limiting yield in early and late sowing respectively.

Wave exposure shapes reef community composition and recovery trajectories at a remote coral atoll - Ines D. Lange; Cassandra E. Benkwitt; Jamie M. McDevitt-Irwin; Kristina L. Tietjen; Brett Taylor; Mark Chinkin; Rachel L. Gunn; Melissa Palmisciano; Margaux Steyaert; Bry Wilson; Holly K. East; John Turner; et al. (Coral Reefs, 2021)
In a time of unprecedented ecological change, understanding natural biophysical relationships between reef resilience and physical drivers is of increasing importance. This study evaluates how wave forcing structures coral reef benthic community composition and recovery trajectories after the major 2015/2016 bleaching event in the remote Chagos Archipelago, Indian Ocean. Benthic cover and substrate rugosity were quantified from digital imagery at 23 fore reef sites around a small coral atoll (Salomon) in 2020 and compared to data from a similar survey in 2006 and opportunistic surveys in intermediate years. Cluster analysis and principal component analysis show strong separation of community composition between exposed (modelled wave exposure > 1000 J m −3 ) and sheltered sites (< 1000 J m −3 ) in 2020. This difference is driven by relatively high cover of Porites sp., other massive corals, encrusting corals, soft corals, rubble and dead table corals at sheltered sites versus high cover of pavement and sponges at exposed sites. Total coral cover and rugosity were also higher at sheltered sites. Adding data from previous years shows benthic community shifts from distinct exposure-driven assemblages and high live coral cover in 2006 towards bare pavement, dead Acropora tables and rubble after the 2015/2016 bleaching event. The subsequent recovery trajectories at sheltered and exposed sites are surprisingly parallel and lead communities towards their respective pre-bleaching communities. These results demonstrate that in the absence of human stressors, community patterns on fore reefs are strongly controlled by wave exposure, even during and after widespread coral loss from bleaching events.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Inter-island differentiation and contrasting patterns of diversity in the iconic Canary Island sub-alpine endemic Echium wildpretii (Boraginaceae) - Rachael E. Graham; J. Alfredo Reyes-Betancort; Mark A. Chapman; Mark A. Carine (Systematics and Biodiversity, 2021)

Responder Needs Addressed by Arctic Maritime Oil Spill Modeling - Jessica Manning; Megan Verfaillie; Christopher Barker; Catherine Berg; Amy MacFadyen; Michael Donnellan; Mark Everett; Clifton Graham; Jason Roe; Nancy Kinner (Journal of Marine Science and Engineering, 2021)
There is a greater probability of more frequent and/or larger oil spills in the Arctic region due to increased maritime shipping and natural resource development. Accordingly, there is an increasing need for effective spilled-oil computer modeling to help emergency oil spill response decision makers, especially in waters where sea ice is present. The National Oceanic & Atmospheric Administration (NOAA) Office of Response & Restoration (OR&R) provides scientific support to the U.S. Coast Guard Federal On-Scene Coordinator (FOSC) during oil spill response. OR&R’s modeling products must provide adequate spill trajectory predictions so that response efforts minimize economic, cultural, and ecologic impacts, including those to species, habitats, and food supplies. The Coastal Response Research Center is conducting a project entitled Oil Spill Modeling for Improved Response to Arctic Maritime Spills: The Path Forward, in conjunction with modelers, responders, and researchers. A goal of the project is to prioritize new investments in model and tool development to improve response effectiveness in the Arctic. The project delineated FOSC needs during Arctic maritime spill response and provided a solution communicating sources of uncertainty in model outputs using a Confidence Estimates of Oil Model Inputs and Outputs (CEOMIO) table. The table shows the level of confidence (high, medium, low) in a model’s trajectory prediction over scenario-specific time intervals and the contribution of different component inputs (e.g., temperature, wind, ice) to that result.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Correction to: Rethinking soil water repellency and its management - Katinka X. Ruthrof; Anna J. M. Hopkins; Melissa Danks; Graham O’Hara; Richard Bell; David Henry; Rachel Standish; Mark Tibbett; John Howieson; Treena Burgess; Richard Harper (Plant Ecology, 2020)

Mismatch repair gene pathogenic germline variants in a population-based cohort of breast cancer - Tu Nguyen-Dumont; Jason A. Steen; Ingrid Winship; Daniel J. Park; Bernard J. Pope; Fleur Hammet; Maryam Mahmoodi; Helen Tsimiklis; Derrick Theys; Mark Clendenning; Graham G. Giles; John L. Hopper; et al. (Familial Cancer, 2020)

Dynamics of a human‐modified tropical peat swamp forest revealed by repeat lidar surveys - Béatrice Wedeux; Michele Dalponte; Michael Schlund; Stephen Hagen; Mark Cochrane; Laura Graham; Aswin Usup; Andri Thomas; David Coomes (Global Change Biology, 2020)
Tropical peat swamp forests (PSFs) are globally important carbon stores under threat. In Southeast Asia, 35% of peatlands had been drained and converted to plantations by 2010, and much of the remaining forest had been logged, contributing significantly to global carbon emissions. Yet, tropical forests have the capacity to regain biomass quickly and forests on drained peatlands may grow faster in response to soil aeration, so the net effect of humans on forest biomass remains poorly understood. In this study, two lidar surveys (made in 2011 and 2014) are compared to map forest biomass dynamics across 96 km 2 of PSF in Kalimantan, Indonesia. The peatland is now legally protected for conservation, but large expanses were logged under concessions until 1998 and illegal logging continues in accessible portions. It was hypothesized that historically logged areas would be recovering biomass while recently logged areas would be losing biomass. We found that historically logged forests were recovering biomass near old canals and railways used by the concessions. Lidar detected substantial illegal logging activity—579 km of logging canals were located beneath the canopy. Some patches close to these canals have been logged in the 2011–2104 period (i.e. substantial biomass loss) but, on aggregate, these illegally logged regions were also recovering. Unexpectedly, rapid growth was also observed in intact forest that had not been logged and was over a kilometre from the nearest known canal, perhaps in response to greater aeration of surface peat. Comparing these results with flux measurements taken at other nearby sites, we find that carbon sequestration in above‐ground biomass may have offset roughly half the carbon efflux from peat oxidation. This study demonstrates the power of repeat lidar survey to map fine‐scale forest dynamics in remote areas, revealing previously unrecognized impacts of anthropogenic global change.

Modelling Eurasian beaver foraging habitat and dam suitability, for predicting the location and number of dams throughout catchments in Great Britain - Hugh A. Graham; Alan Puttock; William W. Macfarlane; Joseph M. Wheaton; Jordan T. Gilbert; Róisín Campbell-Palmer; Mark Elliott; Martin J. Gaywood; Karen Anderson; Richard E. Brazier (European Journal of Wildlife Research, 2020)
Eurasian beaver ( Castor fiber ) populations are expanding across Europe. Depending on location, beaver dams bring multiple benefits and/or require management. Using nationally available data, we developed: a Beaver Forage Index (BFI), identifying beaver foraging habitat, and a Beaver Dam Capacity (BDC) model, classifying suitability of river reaches for dam construction, to estimate location and number of dams at catchment scales. Models were executed across three catchments, in Great Britain (GB), containing beaver. An area of 6747 km 2 was analysed for BFI and 16,739 km of stream for BDC. Field surveys identified 258 km of channel containing beaver activity and 89 dams, providing data to test predictions. Models were evaluated using a categorical binomial Bayesian framework to calculate probability of foraging and dam construction. BFI and BDC models successfully categorised the use of reaches for foraging and damming, with higher scoring reaches being preferred. Highest scoring categories were ca. 31 and 79 times more likely to be used than the lowest for foraging and damming respectively. Zero-inflated negative binomial regression showed that modelled dam capacity was significantly related ( p = 0.01) to observed damming and was used to predict numbers of dams that may occur. Estimated densities of dams, averaged across each catchment, ranged from 0.4 to 1.6 dams/km, though local densities may be up to 30 dams/km. These models provide fundamental information describing the distribution of beaver foraging habitat, where dams may be constructed and how many may occur. This supports the development of policy and management concerning the reintroduction and recolonisation of beaver.

Storm-driven across-shelf oceanic flows into coastal waters - Sam Jones; Mark Inall; Marie Porter; Jennifer A. Graham; Finlo Cottier (Ocean Science, 2020)
The North Atlantic Ocean and northwest European shelf experience intense low-pressure systems during the winter months. The effect of strong winds on shelf circulation and water properties is poorly understood as observations during these episodes are rare, and key flow pathways have been poorly resolved by models up to now. We compare the behaviour of a cross-shelf current in a quiescent period in late summer, with the same current sampled during a stormy period in midwinter, using drogued drifters. Concurrently, high-resolution time series of current speed and salinity from a coastal mooring are analysed. A Lagrangian analysis of modelled particle tracks is used to supplement the observations. Current speeds at 70 m during the summer transit are 10–20 cm s−1, whereas on-shelf flow reaches 60 cm s−1 during the winter storm. The onset of high across-shelf flow is identified in the coastal mooring time series, both as an increase in coastal current speed and as an abrupt increase in salinity from 34.50 to 34.85, which lags the current by 8 d. We interpret this as the wind-driven advection of outer-shelf (near-oceanic) water towards the coastline, which represents a significant change from the coastal water pathways which typically feed the inner shelf. The modelled particle analysis supports this interpretation: particles which terminate in coastal waters are recruited locally during the late summer, but recruitment switches to the outer shelf during the winter storm. We estimate that during intense storm periods, on-shelf transport may be up to 0.48 Sv, but this is near the upper limit of transport based on the multi-year time series of coastal current and salinity. The likelihood of storms capable of producing these effects is much higher during positive North Atlantic Oscillation (NAO) winters.

Synchronous biological feedbacks in parrotfishes associated with pantropical coral bleaching - Brett M. Taylor; Cassandra E. Benkwitt; Howard Choat; Kendall D. Clements; Nicholas A. J. Graham; Mark G. Meekan (Global Change Biology, 2020)
Biological feedbacks generated through patterns of disturbance are vital for sustaining ecosystem states. Recent ocean warming and thermal anomalies have caused pantropical episodes of coral bleaching, which has led to widespread coral mortality and a range of subsequent effects on coral reef communities. Although the response of many reef‐associated fishes to major disturbance events on coral reefs is negative (e.g., reduced abundance and condition), parrotfishes show strong feedbacks after disturbance to living reef structure manifesting as increases in abundance. However, the mechanisms underlying this response are poorly understood. Using biochronological reconstructions of annual otolith (ear stone) growth from two ocean basins, we tested whether parrotfish growth was enhanced following bleaching‐related coral mortality, thus providing an organismal mechanism for demographic changes in populations. Both major feeding guilds of parrotfishes (scrapers and excavators) exhibited enhanced growth of individuals after bleaching that was decoupled from expected thermal performance, a pattern that was not evident in other reef fish taxa from the same environment. These results provide evidence for a more nuanced ecological feedback system—one where disturbance plays a key role in mediating parrotfish–benthos interactions. By influencing the biology of assemblages, disturbance can thereby stimulate change in parrotfish grazing intensity and ultimately reef geomorphology over time. This feedback cycle operated historically at within‐reef scales; however, our results demonstrate that the scale, magnitude, and severity of recent thermal events are entraining the biological responses of disparate communities to respond in synchrony. This may fundamentally alter feedbacks in the relationships between parrotfishes and reef systems.

Density-dependent growth in ‘catch-and-wait’ fisheries has implications for fisheries management and Marine Protected Areas - Julian Merder; Patricia Browne; Jan A. Freund; Liam Fullbrook; Conor Graham; Mark P. Johnson; Alina Wieczorek; Anne Marie Power (Ambio, 2020)
Stock enhancement activities provide an opportunity to examine density-dependent suppression of population biomass which is a fundamental issue for resource management and design of no-take-zones. We document ‘catch-and-wait’ fisheries enhancement where all but the largest lobsters are thrown back, recapturing them later after they have grown to a larger size. The residency, rate of return, and potential negative density-dependent effects of this activity are described using a combination of tagging and v-notching and by relating spatial growth patterns to population density defined with Catch Per Unit Effort. The results successfully demonstrated the concept of catch-and-wait practices. However, a density-dependent suppression of growth (in body size) was observed in male lobsters. This demonstrates a mechanism to explain differences in lobster sizes previously observed across EU fishing grounds with different stock densities. This negative effect of density could also affect individual biomass production in marine reserve or no-take zones.

Perforocycloides nathalieae new genus and species, an unusual Silurian cyclocystoid (Echinodermata) from Anticosti Island, Québec, Canada - Timothy A. M. Ewin; Mike Reich; Mark R. Graham; Mario E. Cournoyer (PalZ, 2019)

Changes in Sex Steroids and Ovarian Steroidogenic Enzyme mRNA Levels in Artificially Maturing Japanese Eel (Anguilla japonica) and Naturally Maturing New Zealand Longfin Eel (Anguilla dieffenbachii) during Vitellogenesis - Hajime Matsubara; P. Mark Lokman; Yukinori Kazeto; Hiromi Okumura; Shigeho Ijiri; Toshiaki Hirai; Graham Young; Shinji Adachi; Kohei Yamauchi (Fishes, 2019)
Repeated hormone injections are routinely used to induce advanced stages of oogenesis in freshwater eels, but this approach may result in aberrant germ cell development. To investigate the underlying causes, levels of sex steroids (testosterone, T; estradiol-17β, E2) and ovarian steroidogenic enzyme mRNAs were compared between artificially maturing Japanese eels and wild-caught, spontaneously maturing New Zealand longfin eels. The latter were employed as reference, as wild Japanese eels in advanced stages of oogenesis are near-impossible to catch. Serum T levels in artificially maturing Japanese eel changed with stage in a pattern that was comparable to that in longfin eels. Likewise, ovarian mRNA levels of most steroidogenic enzyme genes were not qualitatively dissimilar between both eel species when taking developmental stage into account. However, aromatase (cyp19a) mRNA levels, together with serum E2 levels, rapidly increased in artificially maturing Japanese eels in mid-late stages of oogenesis (gonadosomatic index, GSI = 13.8%), whereas no such increase was evident in longfin eels (GSI ~ 6.9%). In addition, sex steroid and target gene mRNA levels fluctuated drastically with each hormone injection. We contend that expression of most target genes, possibly even that of cyp19a, during induced oogenesis could be “normal”, with the drastic fluctuations due most likely to hormone delivery through repeated injections. The effects of these fluctuations on gamete quality remain unknown and resolving this issue may prove fruitful in the future to further artificial propagation of anguillid eels.

Rethinking soil water repellency and its management - Katinka X. Ruthrof; Anna J. M. Hopkins; Melissa Danks; Graham O’Hara; Richard Bell; David Henry; Rachel Standish; Mark Tibbett; John Howieson; Treena Burgess; Richard Harper (Plant Ecology, 2019)

Ability of known susceptibility SNPs to predict colorectal cancer risk for persons with and without a family history - Mark A. Jenkins; Aung K. Win; James G. Dowty; Robert J. MacInnis; Enes Makalic; Daniel F. Schmidt; Gillian S. Dite; Mirosl Kapuscinski; Mark Clendenning; Christophe Rosty; Ingrid M. Winship; Jon D. Emery; et al. (Familial Cancer, 2019)

Overexpression of the MYB29 transcription factor affects aliphatic glucosinolate synthesis in Brassica oleracea - Diana L. Zuluaga; Neil S. Graham; Annett Klinder; A. E. Elaine van Ommen Kloeke; Angelo R. Marcotrigiano; Carol Wagstaff; Ruud Verkerk; Gabriella Sonnante; Mark G. M. Aarts (Plant Molecular Biology, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Modeling groundwater contaminant transport in the presence of large heterogeneity: a case study comparing MT3D and RWhet - Zhilin Guo; Graham E. Fogg; Mark L. Brusseau; Eric M. LaBolle; Jose Lopez (Hydrogeology Journal, 2019)

Bitter taste receptors are expressed in human epithelial ovarian and prostate cancers cells and noscapine stimulation impacts cell survival - Louis T. P. Martin; Mark W. Nachtigal; Tamara Selman; Elaine Nguyen; Jayme Salsman; Graham Dellaire; Denis J. Dupré (Molecular and Cellular Biochemistry, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Presence of an invasive species reverses latitudinal clines of multiple traits in a native species - Christopher J. Thawley; Mark Goldy‐Brown; Gail L. McCormick; Sean P. Graham; Tracy Langkilde (Global Change Biology, 2019)
Understanding the processes driving formation and maintenance of latitudinal clines has become increasingly important in light of accelerating global change. Many studies have focused on the role of abiotic factors, especially temperature, in generating clines, but biotic factors, including the introduction of non‐native species, may also drive clinal variation. We assessed the impact of invasion by predatory fire ants on latitudinal clines in multiple fitness‐relevant traits—morphology, physiological stress responsiveness, and antipredator behavior—in a native fence lizard. In areas invaded by fire ants, a latitudinal cline in morphology is opposite both the cline found in museum specimens from historical populations across the species’ full latitudinal range and that found in current populations uninvaded by fire ants. Similarly, clines in stress‐relevant hormone response to a stressor and in antipredator behavior differ significantly between the portions of the fence lizard range invaded and uninvaded by fire ants. Changes in these traits within fire ant‐invaded areas are adaptive and together support increased and more effective antipredator behavior that allows escape from attacks by this invasive predator. However, these changes may mismatch lizards to the environments under which they historically evolved. This research shows that novel biotic pressures can alter latitudinal clines in multiple traits within a single species on ecological timescales. As global change intensifies, a greater understanding of novel abiotic and biotic pressures and how affected organisms adapt to them across space and time will be central to predicting and managing our changing environment.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

40 Ar/ 39 Ar ages and zircon petrochronology for the rear arc of the Izu-Bonin-Marianas intra-oceanic subduction zone - Axel K. Schmitt; Kevin Konrad; Graham D. M. Andrews; Kenji Horie; Sarah R. Brown; Anthony A. P. Koppers; Mark Pecha; Cathy J. Busby; Yoshihiko Tamura (International Geology Review, 2018)

A role for artificial night-time lighting in long-term changes in populations of 100 widespread macro-moths in UK and Ireland: a citizen-science study - John Fawcett Wilson; David Baker; Janet Cheney; Mike Cook; Martin Ellis; Roger Freestone; David Gardner; Graham Geen; Robin Hemming; Don Hodgers; Stephen Howarth; Ade Jupp; et al. (Journal of Insect Conservation, 2018)

Somatic mutations of the coding microsatellites within the beta-2-microglobulin gene in mismatch repair-deficient colorectal cancers and adenomas - Mark Clendenning; Alvin Huang; Harindra Jayasekara; Marie Lorans; Susan Preston; Neil O’Callaghan; Bernard J. Pope; Finlay A. Macrae; Ingrid M. Winship; Roger L. Milne; Graham G. Giles; Dallas R. English; et al. (Familial Cancer, 2018)

Implications of afforestation for bird communities: the importance of preceding land-use type - Conor T. Graham; Mark W. Wilson; Tom Gittings; Thomas C. Kelly; Sandra Irwin; John L. Quinn; John O’Halloran (Biodiversity and Conservation, 2017)

Trends in anecdotal fox sightings in Tasmania accounted for by psychological factors - Clive A. Marks; Malcolm Clark; David Obendorf; Graham P. Hall; Inês Soares; Filipe Pereira (Conservation Biology, 2017)
There has been little evaluation of anecdotal sightings as a means to confirm new incursions of invasive species. This paper explores the potential for equivocal information communicated by the media to account for patterns of anecdotal reports. In 2001, it was widely reported that red foxes ( Vulpes vulpes ) had been deliberately released in the island state of Tasmania (Australia), although this claim was later revealed to be baseless. Regardless, by 2013 a total of 3153 anecdotal fox sightings had been reported by members of the public, which implied their distribution was wide. For each month in 2001–2003, we defined a monthly media index (MMI) of fox‐related media coverage, an index of their relative seasonal abundance (abundance), and a factor denoting claims of fox evidence (claimed evidence) regardless of its evidentiary quality. We fitted a generalized linear model with Poisson error for monthly totals of anecdotal sightings with factors of year and claimed evidence and covariates of MMI, abundance, and hours of darkness. The collective effect of psychological factors (MMI, claimed evidence, and year) relative to biophysical factors (photoperiod and abundance) was highly significant (χ 2 = 122.1, df = 6, p p = 0.15). An annual index of fox media from 2001 to 2010 was strongly associated with the yearly tally of anecdotal sightings ( p = 0.018). The odds ratio of sightings ranked as reliable by the fox eradication program in any year decreased exponentially at a rate of 0.00643 as the total number of sightings increased ( p

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

The Microbiota, Immunoregulation, and Mental Health: Implications for Public Health - Christopher A. Lowry; David G. Smith; Philip H. Siebler; Dominic Schmidt; Christopher E. Stamper; James E. Hassell; Paula S. Yamashita; James H. Fox; Stefan O. Reber; Lisa A. Brenner; Andrew J. Hoisington; Teodor T. Postolache; et al. (Current Environmental Health Reports, 2016)

Submaximal exercise intensity modulates acute post-exercise heart rate variability - Scott Michael; Ollie Jay; Mark Halaki; Kenneth Graham; Glen M. Davis (European Journal of Applied Physiology, 2016)

Determining the familial risk distribution of colorectal cancer: a data mining approach - Rowena Chau; Mark A. Jenkins; Daniel D. Buchanan; Driss Ait Ouakrim; Graham G. Giles; Graham Casey; Steven Gallinger; Robert W. Haile; Loic Le Marchand; Polly A. Newcomb; Noralane M. Lindor; John L. Hopper; et al. (Familial Cancer, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Risk of colorectal cancer for people with a mutation in both a MUTYH and a DNA mismatch repair gene - Aung Ko Win; Jeanette C. Reece; Daniel D. Buchanan; Mark Clendenning; Joanne P. Young; Sean P. Cleary; Hyeja Kim; Michelle Cotterchio; James G. Dowty; Robert J. MacInnis; Katherine M. Tucker; Ingrid M. Winship; et al. (Familial Cancer, 2015)

Childhood cancers in families with and without Lynch syndrome - John A. Heath; Jeanette C. Reece; Daniel D. Buchanan; Graham Casey; Carol A. Durno; Steven Gallinger; Robert W. Haile; Polly A. Newcomb; John D. Potter; Stephen N. Thibodeau; Loïc Le Marchand; Noralane M. Lindor; et al. (Familial Cancer, 2015)

Disruption and eradication of P. aeruginosa biofilms using nitric oxide-releasing chitosan oligosaccharides - Katelyn P. Reighard; David B. Hill; Graham A. Dixon; Brittany V. Worley; Mark H. Schoenfisch (Biofouling, 2015)

A genome-wide association study for colorectal cancer identifies a risk locus in 14q23.1 - Mathieu Lemire; Conghui Qu; Lenora W. M. Loo; Syed H. E. Zaidi; Hansong Wang; Sonja I. Berndt; Stéphane Bézieau; Hermann Brenner; Peter T. Campbell; Andrew T. Chan; Jenny Chang-Claude; Mengmeng Du; et al. (Human Genetics, 2015)

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

Fine mapping and identification of a candidate gene for the barley Un8 true loose smut resistance gene - Wen Zang; Peter E. Eckstein; Mark Colin; Doug Voth; Axel Himmelbach; Sebastian Beier; Nils Stein; Graham J. Scoles; Aaron D. Beattie (Theoretical and Applied Genetics, 2015)

Supplementary feeding of wild birds indirectly affects ground beetle populations in suburban gardens - Melanie E. Orros; Rebecca L. Thomas; Graham J. Holloway; Mark D. E. Fellowes (Urban Ecosystems, 2015)

The “nutrient pump:” Iron‐poor sediments fuel low nitrogen‐to‐phosphorus ratios and cyanobacterial blooms in polymictic lakes - Diane M. Orihel; David W. Schindler; Nathaniel C. Ballard; Mark D. Graham; David W. O'Connell; Lindsey R. Wilson; Rolf D. Vinebrooke (Limnology and Oceanography, 2015)
Several lines of evidence from a eutrophic lake show how polymixis enables phosphorus (P) released from anoxic, iron (Fe)‐poor sediments to lower nitrogen‐to‐phosphorus (N : P) ratios and stimulate cyanobacterial blooms. Detailed sediment analyses revealed extensive formation of Fe sulfides, which suppressed porewater Fe levels and prevented sequestration of P in Fe minerals. Experimental additions of Fe significantly decreased the flux of dissolved P from warm, anoxic sediments, increasing N : P ratios in porewater and overlying water. The net midsummer effect of polymixis and P release from Fe‐poor sediments quickly doubled the total P in the euphotic zone during a period of very low external P loading. This internal “nutrient pump” decreased N : P in surface waters and led to a cyanobacterial bloom comprised primarily of diazotrophic Anabaena and Aphanizomenon spp. along with nonheterocystous and potentially toxic Microcystis icthyoblabe and Woronichinia naegelianum . Concentrations of the cyanotoxin, microcystin, in this lake were typically elevated during, or shortly after, episodes of internal P loading. Our study demonstrates an important mechanism underlying the increasing cyanobacterial dominance of weakly stratified eutrophic north temperate lakes, and warns of further increases under a warming climate.

Operationalizing resilience for adaptive coral reef management under global environmental change - Kenneth R.N. Anthony; Paul A. Marshall; Ameer Abdulla; Roger Beeden; Chris Bergh; Ryan Black; C. Mark Eakin; Edward T. Game; Margaret Gooch; Nicholas A.J. Graham; Alison Green; Scott F. Heron; et al. (Global Change Biology, 2015)
Cumulative pressures from global climate and ocean change combined with multiple regional and local‐scale stressors pose fundamental challenges to coral reef managers worldwide. Understanding how cumulative stressors affect coral reef vulnerability is critical for successful reef conservation now and in the future. In this review, we present the case that strategically managing for increased ecological resilience (capacity for stress resistance and recovery) can reduce coral reef vulnerability (risk of net decline) up to a point. Specifically, we propose an operational framework for identifying effective management levers to enhance resilience and support management decisions that reduce reef vulnerability. Building on a system understanding of biological and ecological processes that drive resilience of coral reefs in different environmental and socio‐economic settings, we present an Adaptive Resilience‐Based management ( ARBM ) framework and suggest a set of guidelines for how and where resilience can be enhanced via management interventions. We argue that press‐type stressors (pollution, sedimentation, overfishing, ocean warming and acidification) are key threats to coral reef resilience by affecting processes underpinning resistance and recovery, while pulse‐type (acute) stressors (e.g. storms, bleaching events, crown‐of‐thorns starfish outbreaks) increase the demand for resilience. We apply the framework to a set of example problems for Caribbean and Indo‐Pacific reefs. A combined strategy of active risk reduction and resilience support is needed, informed by key management objectives, knowledge of reef ecosystem processes and consideration of environmental and social drivers. As climate change and ocean acidification erode the resilience and increase the vulnerability of coral reefs globally, successful adaptive management of coral reefs will become increasingly difficult. Given limited resources, on‐the‐ground solutions are likely to focus increasingly on actions that support resilience at finer spatial scales, and that are tightly linked to ecosystem goods and services.

Clustering, persistence and control of a pollinator brood disease: epidemiology of A merican foulbrood - Aileen C. Mill; Steven P Rushton; Mark D. F. Shirley; Graham C. Smith; Phil Mason; Mike A. Brown; Giles E. Budge (Environmental Microbiology, 2014)
Summary A merican foulbrood ( AFB ), caused by P aenibacillus larvae , is the most damaging bacterial brood disease of the honeybee ( A pis mellifera ), causing colony deaths on all continents where honeybees are managed. AFB has been a persistent problem in the UK for over 70 years, with a fluctuating number of cases discovered annually. Once diseased colonies are identified, they are destroyed to reduce pathogen spread. We investigated the pattern of AFB cases recorded over the period 1994 to 2012 using spatial‐statistical approaches, with a view to identifying the nature of spread across E ngland and W ales. Our results indicated that AFB exhibits significant spatial aggregation at distances from 10 to 30 km, with aggregations lasting between 1 and 5 years. Kernel smoothing indicated areas of elevated relative risk in different years, and these were further detailed by spatial‐scan statistics. We identified disease clusters and successfully estimated their size, location and duration. The majority of clusters did not persist in all years, indicating that management measures may lead to localized extinction of the disease. Whilst less common, persistent clusters likely indicate potential endemic or exotic risk points. The application of robust epidemiological approaches to improve the control of AFB is discussed.

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Gelatinous zooplankton biomass in the global oceans: geographic variation and environmental drivers - Cathy H. Lucas; Daniel O. B. Jones; Catherine J. Hollyhead; Robert H. Condon; Carlos M. Duarte; William M. Graham; Kelly L. Robinson; Kylie A. Pitt; Mark Schildhauer; Jim Regetz (Global Ecology and Biogeography, 2014)
Aim Scientific debate regarding the future trends, and subsequent ecological, biogeochemical and societal impacts, of gelatinous zooplankton ( GZ ) in a changing ocean is hampered by lack of a global baseline and an understanding of the causes of biogeographic patterns. We address this by using a new global database of GZ records to test hypotheses relating to environmental drivers of biogeographic variation in the multidecadal baseline of epipelagic GZ biomass in the world's oceans. Location Global oceans. Methods Over 476,000 global GZ data and metadata items were assembled from a variety of published and unpublished sources. From this, a total of 91,765 quantitative abundance data items from 1934 to 2011 were converted to carbon biomass using published biometric equations and species‐specific average sizes. Total GZ , Cnidaria, Ctenophora and Chordata (Thaliacea) biomass was mapped into 5° grid cells and environmental drivers of geographic variation were tested using spatial linear models. Results We present JeDI (the J ellyfish D atabase I nitiative), a publically accessible database available at http://jedi.nceas.ucsb.edu . We show that: (1) GZ are present throughout the world's oceans; (2) the global geometric mean and standard deviation of total gelatinous biomass is 0.53 ± 16.16 mg C m −3 , corresponding to a global biomass of 38.3 Tg C in the mixed layer of the ocean; (3) biomass of all gelatinous phyla is greatest in the subtropical and boreal Northern Hemisphere; and (4) within the North Atlantic, dissolved oxygen, apparent oxygen utilization and sea surface temperature are the principal drivers of biomass distribution. Main conclusions JeDI is a unique global dataset of GZ taxa which will provide a benchmark against which future observations can be compared and shifting baselines assessed. The presence of GZ throughout the world's oceans and across the complete global spectrum of environmental variables indicates that evolution has delivered a range of species able to adapt to all available ecological niches.

Adaptations of aortic and pulmonary artery flow parameters measured by phase-contrast magnetic resonance angiography during supine aerobic exercise - Guido E. Pieles; Gergely Szantho; Jonathan C. L. Rodrigues; Christopher B. Lawton; A. Graham Stuart; Chiara Bucciarelli-Ducci; Mark S. Turner; Craig A. Williams; Robert M. R. Tulloh; Mark C. K. Hamilton (European Journal of Applied Physiology, 2014)

Apical-Ventricular Cannula for Aortic Valve Bypass Therapy - Kevin G. Soucy; Joel D. Graham; Carrie J. Benzinger; M. Keith Sharp; Guruprasad A. Giridharan; Michael A. Sobieski; Mark S. Slaughter; Steven C. Koenig (Cardiovascular Engineering and Technology, 2013)

Effects of the serotonergic agonist mCPP on male rats in the quinpirole sensitization model of obsessive–compulsive disorder (OCD) - Mark C. Tucci; Anna Dvorkin-Gheva; Dawn Graham; Sean Amodeo; Paul Cheon; Ashley Kirk; John Peel; Leena Taji; Henry Szechtman (Psychopharmacology, 2013)

Requirements for labelling forest polygons in an object-based image analysis classification - Meghan Graham MacLean; Michael J. Campbell; Daniel S. Maynard; Mark J. Ducey; Russell G. Congalton (International Journal of Remote Sensing, 2013)

The effectiveness of cloning for the genetic improvement of Mexican white cypress Cupressus lusitanica (Mill.) - Heidi S. Dungey; John H. Russell; João Costa e Silva; Charlie B. Low; Mark A. Miller; Kane R. Fleet; Graham T. Stovold (Tree Genetics & Genomes, 2013)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

A live weight–heart girth relationship for accurate dosing of east African shorthorn zebu cattle - Maia Lesosky; Sarah Dumas; Ilana Conradie; Ian Graham Handel; Amy Jennings; Samuel Thumbi; Phillip Toye; Barend Mark de Clare Bronsvoort (Tropical Animal Health and Production, 2012)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Developing cost-effective early detection networks for regional invasions - Alycia W. Crall; Mark Renz; Brendon J. Panke; Gregory J. Newman; Carmen Chapin; Jim Graham; Chuck Bargeron (Biological Invasions, 2012)

Screening practices of Australian men and women categorized as “at or slightly above average risk” of colorectal cancer - Driss Ait Ouakrim; Trevor Lockett; Alex Boussioutas; Louise Keogh; Louisa B. Flander; Ingrid Winship; Graham G. Giles; John L. Hopper; Mark A. Jenkins (Cancer Causes & Control, 2012)

Conserved anchorless surface proteins as group A streptococcal vaccine candidates - Anna Henningham; Emiliano Chiarot; Christine M. Gillen; Jason N. Cole; Manfred Rohde; Marcus Fulde; Vidiya Ramachandran; Amanda J. Cork; Jon Hartas; Graham Magor; Steven P. Djordjevic; Stuart J. Cordwell; et al. (Journal of Molecular Medicine, 2012)

Plant Community Composition and Waterfowl Food Production on Wetland Reserve Program Easements Compared to Those on Managed Public Lands in Western Oregon and Washington - Graham R. Evans-Peters; Bruce D. Dugger; Mark J. Petrie (Wetlands, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Silviculture and Forest Ecology - David Mercker; Ryan Blair; Don Tyler; Theresa Jain; Russell Graham; Donald Rockwood; Nicholas Koch; Jeremy Brawner; Omar Carrero; Kristofer Covey; Alex Barrett; Mark Ashton; et al. (Journal of Forestry, 2011)
2Over the past several decades, federal incentive programs have encouraged the restoration of bottomland forests throughout the West Gulf Coastal Plain (WGCP) and the Lower Mississippi Alluvial Valley (LMAV). Programs such as the Conservation Reserve (CRP) and Wetlands Reserve (WRP) Programs have been marginally successful (Stanturf et al. 2001). Foresters and contractors often follow conventional tree planting procedures that are well established for upland sites, but prove problematic in bottomlands. High water tables, soil drainage and compaction, overland flooding and diverse soil properties make species selection difficult. Slight changes in topography and soil structure often have a dramatic effect on survival and growth of planted oak seedlings (Hodges and Schweitzer 1979). This project documented the survival and growth of six-year old seedlings that were established on a bottomland site in 2004, located at the West Tennessee Research and Education Center, Jackson, Tennessee. The purpose was to determine how soil drainage as indicated by mottling (specifically, the point of 50 percent gray color throughout the soil profile) affects the survival and growth of bottomland oak species. The findings suggest that practitioners plant Nuttall, pin and overcup oaks in poorly drained soils. As the drainage improves, begin mixing in willow oak. In the best drained soils (if they exist), finish by including water, swamp chestnut, swamp white, Shumard, cherrybark and bur oaks. Potential species diversity should expand as the soil drainage improves.

The pro-apoptotic BH3-only protein Bid is dispensable for development of insulitis and diabetes in the non-obese diabetic mouse - Zia U. A. Mollah; Jibran Wali; Mark D. McKenzie; Balasubramanian Krishnamurthy; Kate L. Graham; Stacey Fynch; Joshua Szanyi; Pere Santamaria; Thomas Brodnicki; Janette Allison; Andreas Strasser; Thomas W. H. Kay; et al. (Apoptosis, 2011)

Submarine hydrothermal activity and gold-rich mineralization at Brothers Volcano, Kermadec Arc, New Zealand - Cornel E. J. de Ronde; Gary J. Massoth; David A. Butterfield; Bruce W. Christenson; Junichiro Ishibashi; Robert G. Ditchburn; Mark D. Hannington; Robert L. Brathwaite; John E. Lupton; Vadim S. Kamenetsky; Ian J. Graham; Georg F. Zellmer; et al. (Mineralium Deposita, 2011)

Early-life sun exposure and risk of melanoma before age 40 years - Anne E. Cust; Mark A. Jenkins; Chris Goumas; Bruce K. Armstrong; Helen Schmid; Joanne F. Aitken; Graham G. Giles; Richard F. Kefford; John L. Hopper; Graham J. Mann (Cancer Causes & Control, 2011)

A standardised sampling protocol for robust assessment of reach‐scale fish community diversity in wadeable New Zealand streams - Bruno O David; Mark P Hamer; Kevin J Collier; Mike D Lake; Graham M Surrey; Kate McArthur; Carol Nicholson; Alton Perrie; Matthew Dale (New Zealand Journal of Marine and Freshwater Research, 2010)
The New Zealand fish fauna contains species that are affected not only by river system connectivity, but also by catchment and local‐scale changes in landcover, water quality and habitat quality. Consequently, native fish have potential as multi‐scale bioindicators of human pressure on stream ecosystems, yet no standardised, repeatable and scientifically defensible methods currently exist for effectively quantifying their abundance or diversity in New Zealand stream reaches. Here we report on the testing of a back‐pack electrofishing method, modified from that used by the United States Environmental Protection Agency, on a wide variety of wadeable stream reaches throughout New Zealand. Seventy‐three first‐ to third‐order stream reaches were fished with a single pass over 150–345 m length. Time taken to sample a reach using single‐pass electrofishing ranged from 1–8 h. Species accumulation curves indicated that, irrespective of location, continuous sampling of 150 stream metres is required to accurately describe reach‐scale fish species richness using this approach. Additional species detection beyond 150 m was rare (

Algal-silica cycling and pigment diagenesis in recent alpine lake sediments: mechanisms and paleoecological implications - William O. Hobbs; Stefan V. Lalonde; Rolf D. Vinebrooke; Kurt O. Konhauser; R. Paul Weidman; Mark D. Graham; Alexander P. Wolfe (Journal of Paleolimnology, 2010)

Age-related differences in visual sampling requirements during adaptive locomotion - Graham John Chapman; Mark Andrew Hollands (Experimental Brain Research, 2010)

Dispersal of Contaminant Metals in the Mining-Affected Danube and Maritsa Drainage Basins, Bulgaria, Eastern Europe - Graham Bird; Paul A. Brewer; Mark G. Macklin; Mariyana Nikolova; Tsvetan Kotsev; Mihail Mollov; Catherine Swain (Water, Air, & Soil Pollution, 2010)

Heavy metals in potable groundwater of mining-affected river catchments, northwestern Romania - Graham Bird; Mark G. Macklin; Paul A. Brewer; Sorin Zaharia; Dan Balteanu; Basarab Driga; Mihaela Serban (Environmental Geochemistry and Health, 2009)

Extreme weather events alter planktonic communities in boreal lakes - Mark D. Graham; Rolf D. Vinebrooke (Limnology and Oceanography, 2009)
Climate warming has been shown to increase the frequency of extreme weather effects on small lakes by increasing the variability of terrigenic inputs and surface water temperatures. We hypothesized that the effect of thermal variability on boreal plankton depends on dissolved terrigenic matter (i.e., temperature‐terrigenic interaction). A two‐factor mesocosm (1500‐L capacity) experiment consisting of three terrigenic treatment levels (control, [−] runoff, [+] runoff) and three temperature treatment levels (control, warm, and cold) was conducted in triplicate for a total of 27 mesocosms deployed in Lake 302S of the Experimental Lakes Area in Canada. The warming treatment amplified the positive effect of terrigenic amendment on total phytoplankton biomass by stimulating large (>35‐µm Greatest Axial Linear Dimension; GALD) taxa during the 50‐d experiment. In comparison, removal of terrigenic matter increased the abundance of smaller (

Selective β-adrenergic Receptor Expression on Human Memory CD8+ T Lymphocyte Subsets Regulates Mobilization and INF-y Production - Natalie E. Riddell; Graham R. Wallace; Amber Van Stijn; Rene A. van Lier; Mark T. Drayson; Mike Salmon; Jos A. Bosch (Inflammation Research, 2009)

Musical chairs mortality functions: density-dependent deaths caused by competition for unguarded refuges - Jameal F. Samhouri; Richard R. Vance; Graham E. Forrester; Mark A. Steele (Oecologia, 2009)

Inter‐cohort competition drives density dependence and selective mortality in a marine fish - Jameal F. Samhouri; Mark A. Steele; Graham E. Forrester (Ecology, 2009)
For organisms with complex life cycles, the transition between life stages and between habitats can act as a significant demographic and selective bottleneck. In particular, competition with older and larger conspecifics and heterospecifics may influence the number and characteristics of individuals successfully making the transition. We investigated whether the availability of enemy‐free space mediated the interaction between adult goldspot gobies ( Gnatholepis thompsoni ), a common tropical reef fish, and juvenile conspecifics that had recently settled from the plankton. We added rocks, which provide refuge from predators, to one‐half of each of five entire coral reefs in the Bahamas and measured the survival and growth of recent settlers in relation to adult goby densities. We also evaluated whether mortality was selective with respect to three larval traits (age at settlement, size at settlement, and presettlement growth rate) and measured the influence of refuge availability and adult goby density on selection intensity. Selective mortality was measured by comparing larval traits of newly settled gobies (≤5 d postsettlement) with those of survivors (2–3 week postsettlement juveniles). We detected a negative relationship between juvenile survival and adult goby density in both low‐ and high‐refuge habitats, though experimental refuge addition reduced the intensity of this density dependence. Juvenile growth also declined with increasing adult goby density, but this effect was similar in both low‐ and high‐refuge habitats. Refuge availability had no consistent effect on selective mortality, but adult goby density was significantly related to the intensity of size‐selective mortality: bigger juveniles were favored where adults were abundant, and smaller juveniles were favored where adults were rare. Given the typically large difference in sizes of juveniles and adults, similar stage‐structured interactions may be common but underappreciated in many marine species.

Functional Specialization of Vacuoles in Sugarcane Leaf and Stem - Anne L. Rae; Mark A. Jackson; Chau H. Nguyen; Graham D. Bonnett (Tropical Plant Biology, 2009)

Cumulative impact of GM herbicide-tolerant cropping on arable plants assessed through species-based and functional taxonomies - Geoffrey R. Squire; Cathy Hawes; Graham S. Begg; Mark W. Young (Environmental Science and Pollution Research, 2009)

Species effects on ecosystem processes are modified by faunal responses to habitat composition - Mark T. Bulling; Martin Solan; Kirstie E. Dyson; Gema Hernandez-Milian; Patricia Luque; Graham J. Pierce; Dave Raffaelli; David M. Paterson; Piran C. L. White (Oecologia, 2008)

Climate change causes rapid changes in the distribution and site abundance of birds in winter - ILYA M. D. MACLEAN; GRAHAM E. AUSTIN; MARK M. REHFISCH; JAN BLEW; OLIVIA CROWE; SIMON DELANY; KOEN DEVOS; BERNARD DECEUNINCK; KLAUS GÜNTHER; KARSTEN LAURSEN; MARC VAN ROOMEN; JOHANNES WAHL (Global Change Biology, 2008)
Detecting coherent signals of climate change is best achieved by conducting expansive, long‐term studies. Here, using counts of waders ( Charadrii ) collected from ca. 3500 sites over 30 years and covering a major portion of western Europe, we present the largest‐scale study to show that faunal abundance is influenced by climate in winter. We demonstrate that the ‘weighted centroids’ of populations of seven species of wader occurring in internationally important numbers have undergone substantial shifts of up to 115 km, generally in a northeasterly direction. To our knowledge, this shift is greater than that recorded in any other study, but closer to what would be expected as a result of the spatial distribution of ecological zones. We establish that year‐to‐year changes in site abundance have been positively correlated with concurrent changes in temperature, but that this relationship is most marked towards the colder extremities of the birds' range, suggesting that shifts have occurred as a result of range expansion and that responses to climate change are temperature dependent. Many attempts to model the future impacts of climate change on the distribution of organisms, assume uniform responses or shifts throughout a species' range or with temperature, but our results suggest that this may not be a valid approach. We propose that, with warming temperatures, hitherto unsuitable sites in northeastern Europe will host increasingly important wader numbers, but that this may not be matched by declines elsewhere within the study area. The need to establish that such changes are occurring is accentuated by the statutory importance of this taxon in the designation of protected areas.

SPATIAL DENSITY DEPENDENCE SCALES UP BUT DOES NOT PRODUCE TEMPORAL DENSITY DEPENDENCE IN A REEF FISH - Graham E. Forrester; Mark A. Steele; Jameal F. Samhouri; Bryn Evans; Richard R. Vance (Ecology, 2008)
Field experiments provide rigorous tests of ecological hypotheses but are typically of short duration and use small spatial replicates. We assessed empirically whether the results of experiments testing for density dependence applied at larger spatial domains and explained temporal population dynamics. We studied a small coral reef fish, the goldspot goby ( Gnatholepis thompsoni ), in the Bahamas. We assessed the effects of interactions with conspecifics and with an ecologically similar species, the bridled goby ( Coryphopterus glaucofraenum ). Two density manipulations on small reef patches revealed that goldspot goby mortality over one month increased as conspecifics became crowded. On five large natural reefs, we correlated the initial year‐class density of both species (annual larval settlement) with the subsequent decline of goldspot goby year‐classes for five years. Mortality was correlated with conspecific density among reefs for all years, but not among years for all reefs. Thus, spatial density dependence in mortality scaled up qualitatively from small patches to entire reefs but was not associated with temporal density dependence. Our results support the conclusion that field experiments may be extrapolated to larger spatial domains with care, but that using small spatial comparisons to predict temporal responses is difficult without knowing the underlying biological mechanisms.

Settling larvae of a small coral‐reef fish discriminate reef features at large, but not small, spatial scales - Graham E. Forrester; Mark A. Steele; Jameal F. Samhouri; Richard R. Vance (Limnology and Oceanography, 2008)
Larval settlement of a small coral‐reef fish, the bridled goby ( Coryphopterus glaucofraenum ), to five entire reefs over 4 yr decreased with increasing cover of hard substrate (rock and coral). Experimentally increasing rock cover on these large reefs caused a reduction in settlement that lasted 3 yr, confirming that settling coral‐reef fish discriminate among sites at the mesoscale (hundreds of meters to tens of kilometers). Counterintuitively, a small‐scale manipulation of rock cover and an observational study both suggest that settlers show no response to rock cover at the microscale (few to tens of meters). Habitat selection at settlement can, thus, set initial benthic population size at much larger spatial scales than previously recognized, a finding consistent with the good swimming and sensory capabilities of late‐stage larvae.

Macro‐ to fine‐scale spatial and temporal distributions and dynamics of phytoplankton and their environmental driving forces in a small montane lake in southern California, USA - David A. Caron; Beth Stauffer; Stefanie Moorthi; Amarjeet Singh; Maxim Batalin; Eric A. Graham; Mark Hansen; William J. Kaiser; Jnaneshwar Das; Arvind Pereira; Amit Dhariwal; Bin Zhang; et al. (Limnology and Oceanography, 2008)
A wireless network of buoys, two autonomous robotic boats, and an autonomous tethered vertical profiling system were used to characterize phytoplankton dynamics and spatiotemporal changes in chemical and physical forcing factors in a small montane lake (Lake Fulmor, Idyllwild, California). Three deployments each year were conducted in 2005 and 2006 to examine seasonal changes in the structure of the lake and phytoplankton assemblage, as well as fine‐scale temporal and spatial variations. The buoys yielded fine‐scale temporal patterns of in situ fluorescence and temperature, while the vertical profiling system yielded two‐dimensional, cross‐sectional profiles of several parameters. The autonomous vehicles provided information on fluorescence and corresponding temperature patterns across the surface of the lake. Average, lake‐wide chlorophyll concentrations increased 10‐ fold seasonally, and strong anoxia developed in the hypolimnion during the summer. The latter process dramatically affected vertical chemical gradients in the 5 m water column of the lake. Small‐scale spatial (

Geological control of physical and chemical hydrology in California vernal pools - Mark C. Rains; Randy A. Dahlgren; Graham E. Fogg; Thomas Harter; Robert J. Williamson (Wetlands, 2008)

A hydrodynamic model of Chatham Rise, New Zealand - Mark G. Hadfield; Graham J. Rickard; Michael J. Uddstrom (New Zealand Journal of Marine and Freshwater Research, 2007)
A three‐dimensional hydrodynamic ocean model, the Regional Ocean Modelling System (ROMS), was applied to a region encompassing the Chatham Rise, New Zealand and forced by surface fluxes from an atmospheric reanalysis data set. The model outputs fields were validated against a number of observation‐based data sets, including the CSIRO Atlas of Regional Seas 2000 (CARS 2000) climatology of sub‐surface temperature and salinity, a sea surface temperature (SST) climatology from the NIWA SST Archive (NSA), and sea surface height (SSH) from the Archiving, Validation and Interpretation of Satellite data in Oceanography (AVISO) Mapped Sea Level Anomalies (MSLA) data set. The model reproduced the flow around Chatham Rise well and had a realistic seasonal cycle in the upper ocean. Its biggest deficiency was that the Wairarapa Eddy was too steady and pushed warm water too far south towards the head of Hikurangi Trough. This exercise confirms the need to validate a model against multiple data sets and shows the value of SST data for revealing underlying oceanographic features.

Development of an Ecologic Marine Classification in the New Zealand Region - Ton H. Snelder; John R. Leathwick; Katie L. Dey; Ashley A. Rowden; Mark A. Weatherhead; Graham D. Fenwick; Malcolm P. Francis; Richard M. Gorman; Janet M. Grieve; Mark G. Hadfield; Judi E. Hewitt; Ken M. Richardson; et al. (Environmental Management, 2007)

Multiple anthropogenic stressors cause ecological surprises in boreal lakes - MICHAEL R. CHRISTENSEN; MARK D. GRAHAM; ROLF D. VINEBROOKE; DAVID L. FINDLAY; MICHAEL J. PATERSON; MICHAEL A. TURNER (Global Change Biology, 2006)
The number of combinations of anthropogenic stressors affecting global change is increasing; however, few studies have empirically tested for their interactive effects on ecosystems. Most importantly, interactions among ecological stressors generate nonadditive effects that cannot be easily predicted based on single‐stressor studies. Here, we corroborate findings from an in situ mesocosm experiment with evidence from a whole‐ecosystem manipulation to demonstrate for the first time that interactions between climate and acidification determine their cumulative impact on the food‐web structure of coldwater lakes. Interactions among warming, drought, and acidification, rather than the sum of their individual effects, best explained significant changes in planktonic consumer and producer biomass over a 23‐year period. Further, these stressors interactively exerted significant synergistic and antagonistic effects on consumers and producers, respectively. The observed prevalence of long‐ and short‐term ecological surprises involving the cumulative impacts of multiple anthropogenic stressors highlights the high degree of uncertainty surrounding current forecasts of the consequences of global change.

Assessing the magnitude of intra- and interspecific competition in two coral reef fishes - Graham E. Forrester; Bryn Evans; Mark A. Steele; Richard R. Vance (Oecologia, 2006)

Spatial variation of nitrogen fixation in lakes of the northern Great Plains - Alain Patoine; Mark D. Graham; Peter R. Leavitt (Limnology and Oceanography, 2006)
Cyanobacterial blooms are a regular feature of lakes in central North America, but little is known of their importance to the nitrogen (N) cycle and nutrition of aquatic food webs. We hypothesized that N 2 ‐fixing cyanobacteria constitute a significant source of N to prairie lakes, that fixed N is effectively transferred to primary and secondary consumers, and that the importance of fixed N is structured on a landscape scale due to spatial gradients of lake chemistry and catchment characteristics. These hypotheses were tested using stable isotope analyses and mass budgets in six chained lakes of the northern Great Plains that were sampled biweekly during summers of 1994‐2004. Mean annual N isotope signatures of particulate organic matter (δ 15 N‐POM) were highly correlated to the abundance of N 2 ‐fixing cyanobacteria ( r 2 = 0.75, p , 0.001), but exhibited no marked spatial organization. Instead, the temporal variability of δ 15 N‐POM was greatest in downstream lakes where N 2 ‐fixing cyanobacteria were abundant. Furthermore, seasonal declines in δ 15 N‐POM were correlated with reductions in δ 15 N of individual zooplankton taxa ( Daphnia spp., Diacyclops thomasi , Leptodiaptomus siciloides , Leptodora kindtii ), especially in downstream eastern lakes. N mass balances revealed that the importance of biological N 2 fixation relative to total N inputs (up to 77%) and initial N standing stock (up to 201%) were significantly linearly correlated with landscape position (0.59 ≤ r 2 ≤ 0.83, p ≤ 0.07) and effective drainage area (0.61 ≤ r 2 ≤ 0.98, p ≤ 0.07), as were volumetric and areal estimates of N 2 fixation during summer ( r 2 ≥ 0.87, p ≤ 0.007). These patterns demonstrate that fixed N is spatially structured, highly predictable based on landscape position, and readily assimilated into aquatic food webs.

Accumulation of Selenium and Lack of Severe Effects on Productivity of American Dippers (Cinclus mexicanus) and Spotted Sandpipers (Actitis macularia) - Lee E Harding; Mark Graham; Dale Paton (Archives of Environmental Contamination and Toxicology, 2005)

Shifting nonbreeding distributions of migratory fauna in relation to climatic change - Graham E. Austin; Mark M. Rehfisch (Global Change Biology, 2005)
The distributions of eight out of nine common species of waders (Charadrii) overwintering on UK estuaries have changed in association with recent climate change. These birds represent a high proportion of various populations from breeding grounds as far apart as Greenland to the west to high‐arctic Russia to the east. During warmer winters, smaller proportions of seven species wintered in south‐west Britain. The distributions of the smaller species show the greatest temperature dependence. The opposite was found for the largest species and no relationship was found for a particularly site‐faithful species. In north‐west Europe, the winter isotherms have a broadly north to south alignment, with the east being colder than the west. The average minimum winter temperatures across the UK having increased by about 1.5°C since the mid‐1980s, the temperatures on the east coast during recent winters have been similar to those of the west coast during the mid‐1980s. On average, estuaries on the east and south coasts of Britain have muddier sediments than those on the west coast and thus support a higher biomass of the invertebrate prey of waders. We suggest that, with global climatic change, the advantage gained by waders wintering in the milder west to avoid cold weather‐induced mortality is diminished. Consequently, more choose to winter in the east and thus benefit from better foraging opportunities. The implications of these results are considered in terms of a site‐based approach to wildlife protection used in Europe and elsewhere.

The origin and spread of the HFE-C282Y haemochromatosis mutation - S. Distante; K.J.H. Robson; J. Graham-Campbell; A. Arnaiz-Villena; P. Brissot; Mark Worwood (Human Genetics, 2004)

Effects of halothane, isoflurane, sevoflurane and desflurane on contraction of ventricular myocytes from streptozotocin-induced diabetic rats - Mark Graham; Anwar Qureshi; Rabiah Noueihed; Simon Harrison; Frank Christopher Howarth (Molecular and Cellular Biochemistry, 2004)

Effects of steroid and peptide hormones on in vitro growth of previtellogenic oocytes from eel, Anguilla australis - P. Mark Lokman; Kataraina A.N. George; Graham Young (Fish Physiology and Biochemistry, 2003)

Setting up and optimization of membrane protein simulations - José Faraldo-Gómez; Graham Smith; Mark Sansom (European Biophysics Journal, 2002)

Free energy of a potassium ion in a model of the channel formed by an amphipathic leucine-serine peptide - Graham Smith; Mark Sansom (European Biophysics Journal, 2002)

Electrostatics studies and molecular dynamics simulations of a homology model of the Shaker K + channel pore - Kishani M. Ranatunga; Richard J. Law; Graham R. Smith; Mark S.P. Sansom (European Biophysics Journal, 2001)

Evidence that orexin-A-evoked grooming in the rat is mediated by orexin-1 (OX 1 ) receptors, with downstream 5-HT 2C receptor involvement - Mark S. Duxon; Jennifer Stretton; Kathryn Starr; Declan N.C. Jones; Vicky Holland; Graham Riley; Jeff Jerman; Stephen Brough; Darren Smart; Amanda Johns; Wai Chan; Rod A. Porter; et al. (Psychopharmacology, 2001)

In-frame deletions of BRCA1 may define critical functional domains - Elizabeth Rohlfs; Christine Chung; Qing Yang; Cecile Skrzynia; Wayne Grody; Mark Graham; Lawrence Silverman (Human Genetics, 2000)

The nicotinic acetylcholine receptor: from molecular model to single-channel conductance - Charlotte Adcock; Graham R. Smith; Mark S.P. Sansom (European Biophysics Journal, 2000)

Induced spawning and early ontogeny of New Zealand freshwater eels {Anguilla dieffenbachii and A. australis ) - P. Mark Lokman; Graham Young (New Zealand Journal of Marine and Freshwater Research, 2000)
Knowledge on the reproductive biology of New Zealand freshwater eels ( Anguilla australis Richardson and A. dieffenbachii Gray) is limited to changes associated with gametogenesis in the adults; details pertaining to embryonic and larval development are not available, but are of obvious benefit for a better understanding of the eel life history and for artificial propagation programmes, whether for aquaculture or conservation purposes. Therefore, eels were artificially matured and eggs fertilised with sperm from either species to investigate early ontogeny. Only eggs from A. australis hatched successfully after c. 45 h of incubation at room temperature, yielding larvae of c. 2.5 mm in length. Larvae survived for up to 5 days, by which time they had attained a length of 5.3 mm. Scanning electron microscopy of 1‐ and 2‐day‐old larvae revealed the presence of prominent free neuromasts on the head and along the flanks. Although hatching of New Zealand eels was achieved for the first time, it is strongly recommended that hormone treatment be initiated immediately following capture, well before ovarian atresia starts.

Unprecedented Low Levels of Genetic Variation and Inbreeding Depression in an Island Population of the Black‐Footed Rock‐Wallaby - Mark D. B. Eldridge; Juliet M. King; Anne K. Loupis; Peter B. S. Spencer; Andrea C. Taylor; Lisa C. Pope; Graham P. Hall (Conservation Biology, 1999)
It has been argued that demographic and environmental factors will cause small, isolated populations to become extinct before genetic factors have a significant negative impact. Islands provide an ideal opportunity to test this hypothesis because they often support small, isolated populations that are highly vulnerable to extinction. To assess the potential negative impact of isolation and small population size, we compared levels of genetic variation and fitness in island and mainland populations of the black‐footed rock‐wallaby ( Petrogale lateralis [Marsupialia: Macropodidae]). Our results indicate that the Barrow Island population of P. lateralis has unprecedented low levels of genetic variation ( H e = 0.053, from 10 microsatellite loci) and suffers from inbreeding depression (reduced female fecundity, skewed sex ratio, increased levels of fluctuating asymmetry). Despite a long period of isolation ( ∼ 1600 generations) and small effective population size ( N e ∼ 15), demographic and environmental factors have not yet driven this population to extinction. Nevertheless, it has been affected significantly by genetic factors. It has lost most of its genetic variation and become highly inbred ( F e = 0.91), and it exhibits reduced fitness. Because several other island populations of P. lateralis also exhibit exceptionally low levels of genetic variation, this phenomenon may be widespread. Inbreeding in these populations is at a level associated with high rates of extinction in populations of domestic and laboratory species. Genetic factors cannot then be excluded as contributing to the extinction proneness of small, isolated populations.

No Induction of ?-oxidation in leaves of Arabidopsis that over-produce lauric acid - Mark A. Hooks; Yvonne Fleming; Tony R. Larson; Ian A. Graham (Planta, 1999)

Gonad histology and plasma steroid profiles in wild New Zealand freshwater eels (Anguilla dieffenbachii and A. australis) before and at the onset of the natural spawning migration. I. Females* - P. Mark Lokman; Gerard J. Vermeulen; Jan G.D. Lambert; Graham Young (Fish Physiology and Biochemistry, 1998)

Theoretical modelling of some spatial and temporal aspects of the mitochondrion/creatine kinase/ myofibril system in muscle - Graham J. Kemp; David N. Manners; Joseph F. Clark; Mark E. Bastin; George K. Radda (Molecular and Cellular Biochemistry, 1998)

Diet and alcohol consumption and lung cancer risk in the New York State Cohort (United States) - Elisa V. Bandera; Jo L. Freudenheim; James R. Marshall; Maria Zielezny; Roger L. Priore; John Brasure; Mark Baptiste; Saxon Graham (Cancer Causes & Control, 1997)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)